Austenitic stainless steel alloy welded joint and austenitic stainless steel alloy welding material

By optimizing the chemical composition and welding process of the austenitic stainless steel alloy welded joints, the problem of insufficient resistance of the welded joints in high-temperature corrosion environments is solved, and efficient welding thermal cracking, SCC and corrosiveness are achieved, and the welding joints are improved. aging tenacity.

CN119234050APending Publication Date: 2024-12-31NIPPON STEEL CORPORATION
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202380041634.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-24
Filing Date
2023-05-24
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing austenitic stainless steel alloy welded joints have problems such as insufficient resistance to welding thermal cracks, SCC resistance to polysulfuric acid, corrosion resistance to cycloalkane acid and time-consuming toughness under high-temperature corrosion environment.

Method used

By optimizing the chemical composition of the base material and welded metal of the austenitic stainless steel alloy welded joint, ensuring the specific element content range in the base material and welded metal, and using specific welding process conditions such as TIG welding and protecting the metal electrode arc Welding to form a welded structure with high resistance to welding thermal cracks, resistance to polysulfate SCC, resistance to cycloalkane acid corrosion and excellent aging toughness.

Benefits of technology

It realizes that the welded metal under high-temperature corrosion environment has excellent resistance to welding thermal cracks, resistance to polysulfuric acid SCC, resistance to cycloalkane acid corrosion and aging toughness, extending the service life of the welded joints.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119234050A_ABST
    Figure CN119234050A_ABST
Patent Text Reader

Abstract

Provided is an austenitic stainless steel alloy welded joint containing a weld metal having excellent welding hot cracking resistance, polythionate SCC resistance, naphthenic acid corrosion resistance, and aging toughness. The welding metal (20) contains, in mass%, 0.020% or less of C, 0.01 to 1.00% of Si, 0.20 to 2.00% of Mn, 0.030% or less of P, 0.010% or less of S, 16.0 to 25.0% of Cr, 15.0 to 40.0% of Ni, 2.5 to 5.0% of Mo, 0.10 to 2.00% of Nb, 0.05 to 0.30% of N, 0.001 to 0.100% of sol.Al, and 0.0010 to 0.0050% of B, with F1 as defined by formula (1) being 2.30 or less and F2 as defined by formula (2) being 2.5 or less. F1 = 130B + 8C + 0.025 Cr + 0.25 Mn + 0.08 Mo + 0.6 Nb + 12P + 7.6 S + 0.78 Si + 0.012 W (1), and F2 = [Mo] H / [Mo] L (2).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a weld joint and a welding material, and more particularly to an austenitic stainless steel alloy weld joint and an austenitic stainless steel alloy welding material. Background Art

[0002] Austenitic stainless steel alloy welded joints are manufactured by welding austenitic stainless steel alloy materials. Austenitic stainless steel alloy welded joints contain weld metal and a base material formed by an austenitic stainless steel alloy. Austenitic stainless steel alloy welded joints are used for welded structures of chemical plant equipment such as thermal boilers, oil refining and petrochemical plants. Welded structures of chemical plant equipment are, for example, peripheral equipment of distillation towers, heating furnace tubes, reaction tubes, heat exchangers, piping, etc. Among the components of the welded structures used for these chemical plant equipment, there are components used in a high temperature environment of 600 to 700°C and in an environment containing a corrosive fluid containing sulfides and / or chlorides. In this specification, an environment of a high temperature environment of 600 to 700°C and containing a corrosive fluid containing sulfides and / or chlorides is referred to as a "high temperature corrosion environment".

[0003] Welded structures used in high-temperature corrosive environments are shut down during periodic inspections of chemical plants. When the operation is stopped, the temperature of the welded structure drops to room temperature. At this time, air, moisture, and sulfide films react to generate polythionic acid on the surface of the welded structure. This polythionic acid induces stress corrosion cracking (hereinafter referred to as polythionic acid SCC) at the grain boundaries. Therefore, excellent polythionic acid SCC resistance is required for welded joints, especially weld metals, used in the above-mentioned high-temperature corrosive environment.

[0004] In addition, in chemical plant equipment, when inferior crude oil is used, not only polythionic acid SCC corrosion but also naphthenic acid corrosion may occur. Naphthenic acid is a cyclic saturated hydrocarbon having one or more carboxyl groups. Unlike polythionic acid, naphthenic acid does not cause SCC, but causes general corrosion. Therefore, for the weld metal of the weld joint used in the above-mentioned plant equipment, it is preferred that it has excellent resistance to polythionic acid SCC and excellent resistance to naphthenic acid corrosion.

[0005] Furthermore, the toughness of a welded joint used for a long time in a high temperature environment may decrease. Therefore, excellent aging toughness is required for the weld metal of a welded joint used for a long time in a high temperature environment.

[0006] Furthermore, in the weld metal of the weld joint which is required to have polythionic acid SCC resistance, naphthenic acid corrosion resistance, and aging toughness, it is also required to suppress weld hot cracking during welding.

[0007] Therefore, the weld metal of the austenitic stainless steel alloy weld joint used in the above-mentioned high-temperature corrosion environment is required to have resistance to welding hot cracking, resistance to polythionic acid SCC, resistance to naphthenic acid corrosion, and excellent aging toughness.

[0008] Such alloy materials used in high-temperature corrosive environments are proposed in Japanese Patent Application Laid-Open No. 2003-166039 (Patent Document 1) and International Publication No. 2009 / 044802 (Patent Document 2).

[0009] The austenitic heat-resistant steel disclosed in Patent Document 1 contains, by mass%, C: 0.005% or more and less than 0.03%, Si: 0.05-0.4%, Mn: 0.5-2%, P: 0.01-0.04%, S: 0.0005-0.005%, Cr: 18-20%, Ni: 7-11%, Nb: 0.2-0.5%, V: 0.2-0.5%, Cu: 2-4%, N: 0.10-0.30%, B: 0.0005-0.0080%, and the balance is Fe and unavoidable impurities. The total content of Nb and V is 0.6% or more, and the amount of Nb dissolved in the steel is 0.15% or more. Moreover, N / 14≥Nb / 93+V / 51 and Cr-16C-0.5Nb-V≥17.5 are satisfied. In Patent Document 1, the polythionic acid SCC resistance is improved by reducing the C content and defining the relationship between Cr, C, Nb, and V.

[0010] The austenitic stainless steel disclosed in Patent Document 2 contains, by mass%, C: less than 0.04%, Si: 1.5% or less, Mn: 2% or less, Cr: 15-25%, Ni: 6-30%, N: 0.02-0.35%, Sol.Al: 0.03% or less, and further contains one or more of Nb: 0.5% or less, Ti: 0.4% or less, V: 0.4% or less, Ta: 0.2% or less, Hf: 0.2% or less, and Zr: 0.2% or less, and the balance is Fe and impurities. Among the impurities, P: 0.04% or less, S: 0.03% or less, Sn: 0.1% or less, As: 0.01% or less, Zn: 0.01% or less, Pb: 0.01% or less, and Sb: 0.01% or less. Furthermore, F1=S+{(P+Sn) / 2}+{(As+Zn+Pb+Sb) / 5}≤0.075 and 0.05≤Nb+Ta+Zr+Hf+2Ti+(V / 10)≤1.7-9×F1 are satisfied. In Patent Document 2, the polythionic acid SCC resistance is improved by setting the C content to less than 0.05%. Furthermore, the brittle cracking resistance at the weld heat affected zone (HAZ) is improved by reducing C fixing elements such as Nb and Ti and reducing grain boundary embrittlement elements such as P, S, and Sn in the steel.

[0011] Prior art literature

[0012] Patent Literature

[0013] Patent Document 1: Japanese Patent Application Publication No. 2003-166039

[0014] Patent Document 2: International Publication No. 2009 / 044802 Summary of the invention

[0015] Problem that the invention aims to solve

[0016] However, in Patent Documents 1 and 2, no research is conducted on the weld metal in the weld joint.

[0017] The object of the present disclosure is to provide an austenitic stainless steel alloy weld joint containing a weld metal having excellent resistance to welding hot cracking, resistance to polythionic acid SCC, resistance to naphthenic acid corrosion, and aging toughness, and an austenitic stainless steel alloy welding material used in the austenitic stainless steel alloy weld joint.

[0018] Solutions for solving problems

[0019] The austenitic stainless steel alloy weld joint disclosed in the present invention has the following configuration.

[0020] An austenitic stainless steel alloy welded joint comprising a base material and a weld metal, wherein the chemical composition of the base material is expressed in mass %.

[0021] C: 0.030% or less,

[0022] Si: 0.10-1.00%,

[0023] Mn: 0.20~2.00%,

[0024] P: 0.040% or less,

[0025] S: 0.010% or less,

[0026] Cr: 16.0~25.0%,

[0027] Ni: 10.0-30.0%,

[0028] Mo: 0.1~5.0%,

[0029] Nb: 0.20-1.00%,

[0030] N: 0.05~0.30%,

[0031] Sol.Al: 0.001~0.100%,

[0032] B: 0~0.0080%,

[0033] Cu: 0-5.00%,

[0034] W: 0~5.00%,

[0035] Co: 0-1.00%,

[0036] V: 0~1.00%,

[0037] Ta: 0~0.20%,

[0038] Hf: 0~0.20%,

[0039] Ca: 0~0.010%

[0040] Mg: 0~0.010%,

[0041] Rare earth elements: 0 to 0.100%, and

[0042] The balance is Fe and impurities.

[0043] The chemical composition of the weld metal is expressed in mass % as follows:

[0044] C: 0.020% or less,

[0045] Si: 0.01-1.00%,

[0046] Mn: 0.20~2.00%,

[0047] P: 0.030% or less,

[0048] S: 0.010% or less,

[0049] Cr: 16.0~25.0%,

[0050] Ni: 15.0~40.0%,

[0051] Mo: 2.5-5.0%,

[0052] Nb: 0.10-2.00%,

[0053] N: 0.05~0.30%,

[0054] Sol.Al: 0.001~0.100%,

[0055] B: 0.0010~0.0050%,

[0056] Cu: 0-5.00%,

[0057] W: 0~5.00%,

[0058] Co: 0-1.00%,

[0059] V: 0~1.00%,

[0060] Ta: 0~0.20%,

[0061] Hf: 0~0.20%,

[0062] Ca: 0~0.010%

[0063] Mg: 0~0.010%,

[0064] Rare earth elements: 0 to 0.100%, and

[0065] The balance is Fe and impurities.

[0066] F1 defined by formula (1) in the weld metal is 2.30 or less,

[0067] In a cross section of the weld metal perpendicular to the extending direction of the weld metal, a 1 mm × 1 mm square area at the width center of the surface of the weld metal and at the thickness center of the weld metal is divided into 100 μm × 100 μm micro-square areas, and the Mo content in mass % in each micro-square area is calculated. The arithmetic mean of all the Mo contents obtained is defined as [Mo] AVE , the ratio of the total Mo content obtained to the [Mo] AVE The arithmetic mean of the high Mo content is defined as [Mo] H , the ratio of the total Mo content obtained to the [Mo] AVE The arithmetic mean of the low Mo content is defined as [Mo] L hour,

[0068] F2 defined by formula (2) is less than 2.5,

[0069] F1=130B+8C+0.025Cr+0.25Mn+0.08Mo+0.6Nb+12P+7.6S+0.78Si+0.012W (1)

[0070] F2=[Mo] H / [Mo] L (2)

[0071] In the formula (1), the content of the corresponding element in the weld metal is substituted in mass %.

[0072] The austenitic stainless steel alloy welding material disclosed in the present invention has the following configuration.

[0073] An austenitic stainless steel alloy welding material, the chemical composition of which is expressed in mass %

[0074] C: 0.020% or less,

[0075] Si: 0.01-1.00%,

[0076] Mn: 0.20~2.00%,

[0077] P: 0.030% or less,

[0078] S: 0.010% or less,

[0079] Cr: 16.0~25.0%,

[0080] Ni: 15.0~40.0%,

[0081] Mo: 2.5-5.0%,

[0082] Nb: 0.10-2.00%,

[0083] N: 0.05~0.30%,

[0084] Sol.Al: 0.001~0.100%,

[0085] B: 0.0010~0.0050%,

[0086] Cu: 0-5.00%,

[0087] W: 0~5.00%,

[0088] Co: 0-1.00%,

[0089] V: 0~1.00%,

[0090] Ta: 0~0.20%,

[0091] Hf: 0~0.20%,

[0092] Ca: 0~0.010%

[0093] Mg: 0~0.010%,

[0094] Rare earth elements: 0 to 0.100%, and the balance is Fe and impurities.

[0095] Effects of the Invention

[0096] The weld metal of the austenitic stainless steel alloy welded joint disclosed herein has excellent weld hot cracking resistance, polythionic acid SCC resistance, naphthenic acid corrosion resistance, and aging toughness. The austenitic stainless steel alloy welding material disclosed herein is a raw material of the weld metal having the above-mentioned effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0097] Figure 1 It is a plan view showing an example of an austenitic stainless steel alloy weld joint according to the present embodiment.

[0098] Figure 2 Cutting in the width direction of the weld metal Figure 1 Cross-section of an austenitic stainless steel alloy weld joint.

[0099] Figure 3 Cutting is done in the direction of the weld metal extension. Figure 1 Cross-section of an austenitic stainless steel alloy weld joint.

[0100] Figure 4 is with Figure 3 Different cross-sectional views of austenitic stainless steel alloy weld joints cut in the direction of the weld metal extension.

[0101] Figure 5 This is a cross-sectional view perpendicular to the extending direction of the weld metal of the austenitic stainless steel alloy weld joint according to the present embodiment.

[0102] Figure 6 It is a schematic diagram for explaining the groove shape of the parent material in the embodiment.

[0103] Figure 7 It is used Figure 6 Schematic diagram of the welded joint of the base material.

[0104] Figure 8 It is a schematic diagram which shows the sampling position of the plate-shaped test piece used in the Example.

[0105] Fig. 9 It is a schematic diagram which shows the sampling position of the V-notch test piece used in the Example. DETAILED DESCRIPTION

[0106] The present inventors have studied methods for improving the weld hot cracking resistance, polythionic acid SCC resistance, naphthenic acid corrosion resistance, and aging toughness of weld metals of austenitic stainless steel alloy weld joints. As a result, the inventors have obtained the following findings.

[0107] The inventors of the present invention first studied the chemical composition of the base material constituting the austenitic stainless steel alloy welded joint. As a result, it is believed that from the viewpoints of weld metal, weld hot cracking resistance, polythionic acid SCC resistance, naphthenic acid corrosion resistance, and aging toughness, it is appropriate for the base material of the austenitic stainless steel alloy welded joint to satisfy the following characteristic 1.

[0108] (Feature 1)

[0109] The chemical composition of the base material is as follows by mass %: C: 0.030% or less, Si: 0.10-1.00%, Mn: 0.20-2.00%, P: 0.040% or less, S: 0.010% or less, Cr: 16.0-25.0%, Ni: 10.0-30.0%, Mo: 0.1-5.0%, Nb: 0.20-1.00%, N: 0.05-0.30%, So l.Al: 0.001~0.100%, B: 0~0.0080%, Cu: 0~5.00%, W: 0~5.00%, Co: 0~1.00%, V: 0~1.00%, Ta: 0~0.20%, Hf: 0~0.20%, Ca: 0~0.010%, Mg: 0~0.010%, rare earth elements: 0~0.100%, and the balance is Fe and impurities.

[0110] The inventors have also studied the chemical composition of the weld metal of the austenitic stainless steel alloy weld joint. As a result, it is believed that the chemical composition of the weld metal satisfies the following characteristic 2, which improves the weld hot cracking resistance, polythionic acid SCC resistance, naphthenic acid corrosion resistance, and aging toughness.

[0111] (Feature 2)

[0112] The chemical composition of the weld metal is as follows by mass %: C: 0.020% or less, Si: 0.01-1.00%, Mn: 0.20-2.00%, P: 0.030% or less, S: 0.010% or less, Cr: 16.0-25.0%, Ni: 15.0-40.0%, Mo: 2.5-5.0%, Nb: 0.10-2.00%, N: 0.05-0.30%, sol .Al: 0.001~0.100%, B: 0.0010~0.0050%, Cu: 0~5.00%, W: 0~5.00%, Co: 0~1.00%, V: 0~1.00%, Ta: 0~0.20%, Hf: 0~0.20%, Ca: 0~0.010%, Mg: 0~0.010%, rare earth elements: 0~0.100%, and the balance is Fe and impurities.

[0113] However, even in a welded joint of a base metal having the above chemical composition and a weld metal having the above chemical composition, there are still cases where none of the weld hot cracking resistance, polythionic acid SCC resistance, naphthenic acid corrosion resistance, and aging toughness cannot be sufficiently obtained in the weld metal. The weld metal is formed by welding. In this respect, it is different from the base metal produced by hot working. Therefore, it is effective to improve the weld hot cracking resistance, polythionic acid SCC resistance, naphthenic acid corrosion resistance, and aging toughness in the weld metal by a method different from that of the base metal.

[0114] Therefore, the present inventors have further studied methods for improving the weld hot cracking resistance, polythionic acid SCC resistance, naphthenic acid corrosion resistance, and aging toughness in the weld metal. As a result, it was found that the weld hot cracking resistance, polythionic acid SCC resistance, naphthenic acid corrosion resistance, and aging toughness are sufficiently improved in the weld metal of the weld joint by further satisfying the following characteristics 3 and 4 in the weld metal of the weld joint.

[0115] (Feature 3)

[0116] F1 of the weld metal defined by formula (1) is 2.30 or less.

[0117] F1=130B+8C+0.025Cr+0.25Mn+0.08Mo+0.6Nb+12P+7.6S+0.78Si+0.012W(1)

[0118] In the formula (1), the content of the corresponding element in the weld metal is substituted in mass %.

[0119] (Feature 4)

[0120] In a cross section of the weld metal perpendicular to the extending direction of the weld metal, a 1 mm × 1 mm square area at the center of the width of the surface of the weld metal and at the center of the thickness of the weld metal is divided into small square areas of 100 μm × 100 μm, and the Mo content in mass % in each small square area is calculated. The arithmetic mean of all the Mo contents obtained is defined as [Mo] AVE , the total Mo content obtained is [Mo] AVE The arithmetic mean of the high Mo content is defined as [Mo] H , the total Mo content obtained is [Mo] AVE The arithmetic mean of the low Mo content is defined as [Mo] L When F2 defined by formula (2) is less than 2.5.

[0121] F2=[Mo] H / [Mo] L (2)

[0122] The austenitic stainless steel alloy welded joint and the austenitic stainless steel alloy welding material according to the present embodiment, which have been completed based on the above findings, have the following configurations.

[0123] [1] An austenitic stainless steel alloy welded joint comprising a base metal and a weld metal, wherein the chemical composition of the base metal is, in mass %,

[0124] C: 0.030% or less,

[0125] Si: 0.10-1.00%,

[0126] Mn: 0.20~2.00%,

[0127] P: 0.040% or less,

[0128] S: 0.010% or less,

[0129] Cr: 16.0~25.0%,

[0130] Ni: 10.0-30.0%,

[0131] Mo: 0.1~5.0%,

[0132] Nb: 0.20-1.00%,

[0133] N: 0.05~0.30%,

[0134] Sol.Al: 0.001~0.100%,

[0135] B: 0~0.0080%,

[0136] Cu: 0-5.00%,

[0137] W: 0~5.00%,

[0138] Co: 0-1.00%,

[0139] V: 0~1.00%,

[0140] Ta: 0~0.20%,

[0141] Hf: 0~0.20%,

[0142] Ca: 0~0.010%

[0143] Mg: 0~0.010%,

[0144] Rare earth elements: 0 to 0.100%, and

[0145] The balance is Fe and impurities.

[0146] The chemical composition of the weld metal is expressed in mass % as follows:

[0147] C: 0.020% or less,

[0148] Si: 0.01-1.00%,

[0149] Mn: 0.20~2.00%,

[0150] P: 0.030% or less,

[0151] S: 0.010% or less,

[0152] Cr: 16.0~25.0%,

[0153] Ni: 15.0~40.0%,

[0154] Mo: 2.5-5.0%,

[0155] Nb: 0.10-2.00%,

[0156] N: 0.05~0.30%,

[0157] Sol.Al: 0.001~0.100%,

[0158] B: 0.0010~0.0050%,

[0159] Cu: 0-5.00%,

[0160] W: 0~5.00%,

[0161] Co: 0-1.00%,

[0162] V: 0~1.00%,

[0163] Ta: 0~0.20%,

[0164] Hf: 0~0.20%,

[0165] Ca: 0~0.010%

[0166] Mg: 0~0.010%,

[0167] Rare earth elements: 0 to 0.100%, and

[0168] The balance is Fe and impurities.

[0169] The F1 of the weld metal defined by formula (1) is 2.30 or less,

[0170] In a cross section of the weld metal perpendicular to the extending direction of the weld metal, a 1 mm×1 mm square area at the center of the width of the surface of the weld metal and at the center of the thickness of the weld metal is divided into small square areas of 100 μm×100 μm, and the Mo content in mass % in each small square area is calculated, and the arithmetic mean value of all the Mo contents obtained is defined as [Mo] AVE , among all the Mo contents obtained, the ratio of [Mo] AVE The arithmetic mean of the high Mo content is defined as [Mo]H , among all the Mo contents obtained, the ratio of [Mo] AVE The arithmetic mean of the low Mo content is defined as [Mo] L hour,

[0171] F2 defined by formula (2) is less than 2.5,

[0172] F1=130B+8C+0.025Cr+0.25Mn+0.08Mo+0.6Nb+12P+7.6S+0.78Si+0.012W (1)

[0173] F2=[Mo] H / [Mo] L (2)

[0174] In the formula (1), the content of the corresponding element in the weld metal is substituted in mass %.

[0175] [2] The austenitic stainless steel alloy welded joint according to [1], wherein:

[0176] The chemical composition of the base material contains

[0177] B: 0.0001~0.0080%,

[0178] Cu: 0.01~5.00%,

[0179] W: 0.01~5.00%,

[0180] Co: 0.01~1.00%,

[0181] V: 0.01~1.00%,

[0182] Ta: 0.01~0.20%

[0183] Hf: 0.01~0.20%,

[0184] Ca: 0.001~0.010%,

[0185] Mg: 0.001-0.010%, and

[0186] Rare earth elements: one or more elements selected from the group consisting of 0.001 to 0.100%.

[0187] [3] The austenitic stainless steel alloy welded joint according to [1] or [2], wherein:

[0188] The chemical composition of the weld metal contains

[0189] Cu: 0.01~5.00%,

[0190] W: 0.01~5.00%,

[0191] Co: 0.01~1.00%,

[0192] V: 0.01~1.00%,

[0193] Ta: 0.01~0.20%

[0194] Hf: 0.01~0.20%,

[0195] Ca: 0.001~0.010%,

[0196] Mg: 0.001-0.010%, and

[0197] Rare earth elements: one or more elements selected from the group consisting of 0 to 0.100%.

[0198] [4] An austenitic stainless steel alloy welding material having a chemical composition in mass % of

[0199] C: 0.020% or less,

[0200] Si: 0.01-1.00%,

[0201] Mn: 0.20~2.00%,

[0202] P: 0.030% or less,

[0203] S: 0.010% or less,

[0204] Cr: 16.0~25.0%,

[0205] Ni: 15.0~40.0%,

[0206] Mo: 2.5-5.0%,

[0207] Nb: 0.10-2.00%,

[0208] N: 0.05~0.30%,

[0209] Sol.Al: 0.001~0.100%,

[0210] B: 0.0010~0.0050%,

[0211] Cu: 0-5.00%,

[0212] W: 0~5.00%,

[0213] Co: 0-1.00%,

[0214] V: 0~1.00%,

[0215] Ta: 0~0.20%,

[0216] Hf: 0~0.20%,

[0217] Ca: 0~0.010%

[0218] Mg: 0~0.010%,

[0219] Rare earth elements: 0 to 0.100%, and

[0220] The balance is Fe and impurities.

[0221] The austenitic stainless steel alloy welded joint and the austenitic stainless steel alloy welding material according to the present embodiment will be described in detail below. In this specification, "%" related to an element means mass % unless otherwise specified.

[0222] [Composition of Austenitic Stainless Steel Alloy Welded Joints]

[0223] Figure 1 1 is a plan view showing an example of an austenitic stainless steel alloy weld joint 1 according to the present embodiment. Figure 1 The austenitic stainless steel alloy welded joint 1 of the present embodiment includes a base material 10 and a weld metal 20. The weld metal 20 is formed by butting the ends of a pair of base materials 10 whose ends are grooved and then welding them. Examples of welding include TIG welding (Gas Tungsten Arc Welding: GTAW), shielded metal arc welding (Shielded Metal Arc Welding: SMAW), flux cored arc welding (Flux Cored Arc Welding: FCAW), gas metal arc welding (Gas Metal Arc Welding: GMAW), and submerged arc welding (Submerged Arc Welding: SAW).

[0224] exist Figure 1 , the direction in which the weld metal 20 extends is defined as the weld metal extending direction L. The direction perpendicular to the weld metal extending direction L when viewed from above is defined as the weld metal width direction W. The direction perpendicular to the weld metal extending direction L and the weld metal width direction W is defined as the weld metal thickness direction T. Figure 2 Cutting in the width direction W of the weld metal Figure 1 A cross-sectional view of an austenitic stainless steel alloy welded joint 1. Figure 1 and Figure 2 As shown, the weld metal 20 is arranged between a pair of base materials 10 .

[0225] Figure 3 Cutting is done in the direction L of the weld metal extension Figure 1 Cross-sectional view of an austenitic stainless steel alloy welded joint 1. Figure 4 is with Figure 3 Different cross-sectional views of the austenitic stainless steel alloy welded joint 1 cut along the weld metal extension direction L. Figure 3 As shown in FIG. 1 , the shape of the base material 10 may also be a plate. Figure 4 As shown, the base material 10 may be in the shape of an alloy tube. The base material 10 may be in the shape of a bar or a steel shape, but this is not shown.

[0226] [Features of the Austenitic Stainless Steel Alloy Welded Joint 1 of the Present Embodiment]

[0227] The austenitic stainless steel alloy weld joint 1 of the present embodiment satisfies the following features 1 to 4.

[0228] (Feature 1)

[0229] The chemical composition of the base material 10 is, in mass%, C: 0.030% or less, Si: 0.10 to 1.00%, Mn: 0.20 to 2.00%, P: 0.040% or less, S: 0.010% or less, Cr: 16.0 to 25.0%, Ni: 10.0 to 30.0%, Mo: 0.1 to 5.0%, Nb: 0.20 to 1.00%, N: 0.05 to 0.30%, S ol.Al: 0.001~0.100%, B: 0~0.0080%, Cu: 0~5.00%, W: 0~5.00%, Co: 0~1.00%, V: 0~1.00%, Ta: 0~0.20%, Hf: 0~0.20%, Ca: 0~0.010%, Mg: 0~0.010%, rare earth elements: 0~0.100%, and the balance is Fe and impurities.

[0230] (Feature 2)

[0231] The chemical composition of the weld metal 20 is, by mass%, C: 0.020% or less, Si: 0.01 to 1.00%, Mn: 0.20 to 2.00%, P: 0.030% or less, S: 0.010% or less, Cr: 16.0 to 25.0%, Ni: 15.0 to 40.0%, Mo: 2.5 to 5.0%, Nb: 0.10 to 2.00%, N: 0.05 to 0.30%, and so l.Al: 0.001~0.100%, B: 0.0010~0.0050%, Cu: 0~5.00%, W: 0~5.00%, Co: 0~1.00%, V: 0~1.00%, Ta: 0~0.20%, Hf: 0~0.20%, Ca: 0~0.010%, Mg: 0~0.010%, rare earth elements: 0~0.100%, and the balance is Fe and impurities.

[0232] (Feature 3)

[0233] F1 of the weld metal 20 defined by the formula (1) is 2.30 or less.

[0234] F1=130B+8C+0.025Cr+0.25Mn+0.08Mo+0.6Nb+12P+7.6S+0.78Si+0.012W(1)

[0235] In the formula (1), the content of the corresponding element in the weld metal 20 is substituted in mass %.

[0236] (Feature 4)

[0237] In a cross section of the weld metal perpendicular to the extending direction of the weld metal 20, a 1 mm × 1 mm square area at the center of the width of the surface of the weld metal and at the center of the thickness of the weld metal is divided into small square areas of 100 μm × 100 μm, and the Mo content in mass % in each small square area is calculated. The arithmetic mean of all the Mo contents obtained is defined as [Mo] AVE , the total Mo content obtained is [Mo] AVE The arithmetic mean of the high Mo content is defined as [Mo] H , the total Mo content obtained is [Mo] AVE The arithmetic mean of the low Mo content is defined as [Mo] L When F2 defined by formula (2) is less than 2.5.

[0238] F2=[Mo] H / [Mo] L (2)

[0239] Hereinafter, features 1 to 4 will be described respectively.

[0240] [Regarding (Feature 1) Chemical Composition of Base Material 10]

[0241] The chemical composition of the base material 10 of the austenitic stainless steel alloy weld joint 1 of the present embodiment contains the following elements.

[0242] C: 0.030% or less

[0243] The base material 10 inevitably contains carbon (C). That is, the C content is greater than 0%. When used in a high-temperature corrosive environment of 600 to 700°C, C forms Cr carbides (M) at the grain boundaries of the base material 10. 23 C 6 Type carbide). Due to the formation of Cr carbides, the solid solution Cr is reduced. Therefore, the polythionic acid SCC resistance of the base material 10 is reduced. Therefore, the C content is 0.030% or less.

[0244] The C content is preferably as low as possible. However, excessive reduction of the C content will increase the production cost. Therefore, in industrial production, the preferred lower limit of the C content is 0.001%, and more preferably 0.002%.

[0245] The upper limit of the C content is preferably 0.025%, more preferably 0.020%, more preferably 0.018%, more preferably 0.016%, and further preferably 0.015%.

[0246] Si: 0.10~1.00%

[0247] Silicon (Si) deoxidizes the alloy. If the Si content is less than 0.10%, even if the contents of other elements are within the range of the present embodiment, the above-mentioned effects cannot be fully obtained. On the other hand, if the Si content is greater than 1.00%, sigma phase (σ phase) precipitates in the base material 10, and the aging toughness of the alloy decreases. Therefore, the Si content is 0.10 to 1.00%.

[0248] The lower limit of the Si content is preferably 0.15%, more preferably 0.17%, more preferably 0.18%, more preferably 0.20%, and still more preferably 0.25%.

[0249] The upper limit of the Si content is preferably 0.95%, more preferably 0.90%, more preferably 0.85%, more preferably 0.80%, more preferably 0.75%, more preferably 0.70%, more preferably 0.50%, and more preferably 0.45%.

[0250] Mn: 0.20~2.00%

[0251] Manganese (Mn) deoxidizes the alloy. Mn also stabilizes austenite and suppresses the decrease in aging toughness of the base material 10. If the Mn content is less than 0.20%, even if the contents of other elements are within the range of the present embodiment, the above-mentioned effects cannot be fully obtained. On the other hand, if the Mn content is greater than 2.00%, the high temperature strength of the base material 10 decreases. Therefore, the Mn content is 0.20 to 2.00%.

[0252] The lower limit of the Mn content is preferably 0.30%, more preferably 0.35%, more preferably 0.40%, more preferably 0.50%, more preferably 0.60%, more preferably 0.70%, and more preferably 0.80%.

[0253] The upper limit of the Mn content is preferably 1.90%, more preferably 1.85%, more preferably 1.80%, more preferably 1.75%, more preferably 1.70%, more preferably 1.60%, and more preferably 1.50%.

[0254] P: 0.040% or less

[0255] Phosphorus (P) is an impurity that is inevitably contained. That is, the P content is greater than 0%. If the P content is greater than 0.040%, the welding hot crack resistance of the base material 10 will decrease even if the contents of other elements are within the range of the present embodiment. Therefore, the P content is 0.040% or less.

[0256] The P content is preferably as low as possible. However, excessive reduction of the P content will increase the manufacturing cost. Therefore, in industrial production, the preferred lower limit of the P content is 0.001%, and more preferably 0.002%.

[0257] The upper limit of the P content is preferably 0.035%, more preferably 0.032%, further preferably 0.028%, further preferably 0.026%.

[0258] S: 0.010% or less

[0259] Sulfur (S) is an impurity that is inevitably contained. That is, the S content is greater than 0%. If the S content is greater than 0.010%, the welding hot crack resistance of the base material 10 will decrease even if the contents of other elements are within the range of the present embodiment. Therefore, the S content is 0.010% or less.

[0260] The S content is preferably as low as possible. However, excessive reduction of the S content will increase the manufacturing cost. Therefore, in industrial production, the preferred lower limit of the S content is 0.001%.

[0261] The upper limit of the S content is preferably 0.007%, more preferably 0.006%, more preferably 0.005%, more preferably 0.004%, and still more preferably 0.003%.

[0262] Cr: 16.0~25.0%

[0263] Chromium (Cr) improves the polythionic acid SCC resistance of the base material 10. If the Cr content is less than 16.0%, the above-mentioned effect cannot be fully obtained even if the contents of other elements are within the range of the present embodiment. On the other hand, if the Cr content is more than 25.0%, the aging toughness of the base material 10 decreases. Therefore, the Cr content is 16.0 to 25.0%.

[0264] The lower limit of the Cr content is preferably 16.5%, more preferably 17.0%, further preferably 17.2%, further preferably 17.4%.

[0265] The upper limit of the Cr content is preferably 24.0%, more preferably 23.0%, and further preferably 22.0%.

[0266] Ni: 10.0~30.0%

[0267] Nickel (Ni) stabilizes austenite and improves the aging toughness of the base material 10. If the Ni content is less than 10.0%, the above effect cannot be fully obtained even if the content of other elements is within the range of the present embodiment. On the other hand, if the Ni content is greater than 30.0%, the above effect is saturated, and the manufacturing cost becomes high. Therefore, the Ni content is 10.0 to 30.0%.

[0268] The lower limit of the Ni content is preferably 11.0%, more preferably 12.0%, further preferably 13.0%, further preferably 13.5%.

[0269] The preferred upper limit of the Ni content is 27.0%, more preferably 26.0%, more preferably 25.0%, more preferably 22.0%, more preferably 20.0%, more preferably 18.0%, and more preferably 17.0%.

[0270] Mo: 0.1~5.0%

[0271] Regarding molybdenum (Mo), when used in a high-temperature corrosive environment of 600 to 700°C, the solid-solution Mo in the base material 10 combines with S in the use environment to form a sulfide film on the surface of the base material 10. Due to the formation of this sulfide film, the cyclopentane acid corrosion resistance is improved. If the Mo content is less than 0.1%, even if the content of other elements is within the range of the present embodiment, the above-mentioned effects cannot be fully obtained. On the other hand, if the Mo content is greater than 5.0%, there is a situation where welding hot cracks are generated in the HAZ during welding, or the aging toughness is reduced. Therefore, the Mo content is 0.1 to 5.0%.

[0272] The lower limit of the Mo content is preferably 0.2%, more preferably 0.3%, more preferably 0.5%, more preferably 1.0%, more preferably 1.5%, and more preferably 2.0%.

[0273] The upper limit of the Mo content is preferably 4.5%, more preferably 4.0%.

[0274] Nb: 0.20~1.00%

[0275] Niobium (Nb) combines with C to form MX-type carbonitrides during use in a high-temperature corrosive environment of 600 to 700°C, and the amount of solid-solubilized C in the base material 10 is reduced. As a result, the polythionic acid SCC resistance of the base material 10 is improved. If the Nb content is less than 0.20%, even if the contents of other elements are within the range of the present embodiment, the above-mentioned effects cannot be fully obtained. On the other hand, if the Nb content is greater than 1.00%, delta ferrite is generated, and the aging toughness of the base material 10 is reduced. Therefore, the Nb content is 0.20 to 1.00%.

[0276] The lower limit of the Nb content is preferably 0.25%, more preferably 0.28%, further preferably 0.30%, further preferably 0.32%.

[0277] The upper limit of the Nb content is preferably 0.90%, more preferably 0.85%, more preferably 0.80%, more preferably 0.70%, and still more preferably 0.65%.

[0278] N: 0.05~0.30%

[0279] Nitrogen (N) is dissolved in the matrix (parent phase) to stabilize austenite and improve the high temperature strength of the base material 10. N also forms fine carbonitrides in the grains to improve the high temperature strength of the base material 10. If the N content is less than 0.05%, even if the contents of other elements are within the range of the present embodiment, the above-mentioned effects cannot be fully obtained. On the other hand, if the N content is greater than 0.30%, Cr nitrides are generated at the grain boundaries. In this case, the polythionic acid SCC resistance and cyclohexane acid corrosion resistance at the weld heat affected zone (HAZ) of the base material 10 are reduced. Therefore, the N content is 0.05 to 0.30%.

[0280] The lower limit of the N content is preferably 0.06%, more preferably 0.07%, further preferably 0.08%, further preferably 0.10%.

[0281] The upper limit of the N content is preferably 0.25%, more preferably 0.20%, and further preferably 0.19%.

[0282] Sol.Al: 0.001~0.100%

[0283] Aluminum (Al) deoxidizes the alloy. If the Al content is less than 0.001%, the above-mentioned effects cannot be fully obtained even if the contents of other elements are within the range of the present embodiment. On the other hand, if the Al content is greater than 0.100%, the cleanliness of the alloy decreases, and the workability and ductility of the alloy decrease. Therefore, the Al content is 0.001 to 0.100%.

[0284] The lower limit of the Al content is preferably 0.002%, more preferably 0.003%.

[0285] The upper limit of the Al content is preferably 0.050%, more preferably 0.030%, further preferably 0.026%, further preferably 0.025%.

[0286] In the present embodiment, the Al content refers to the content of acid-soluble Al (sol. Al).

[0287] The balance of the chemical composition of the base material 10 of the austenitic stainless steel alloy welded joint 1 of the present embodiment is Fe and impurities. Here, impurities refer to elements mixed from ore, waste materials, or manufacturing environment as raw materials when the base material 10 is industrially manufactured, and are not intentionally contained elements, but are allowed elements within a range that does not adversely affect the base material 10 of the austenitic stainless steel alloy welded joint 1 of the present embodiment.

[0288] [Optional Elements]

[0289] The chemical composition of the base material 10 of the austenitic stainless steel alloy weld joint 1 of the present embodiment may further contain a

[0290] B: 0~0.0080%,

[0291] Cu: 0-5.00%,

[0292] W: 0~5.00%,

[0293] Co: 0-1.00%,

[0294] V: 0~1.00%,

[0295] Ta: 0~0.20%,

[0296] Hf: 0~0.20%,

[0297] Ca: 0~0.010%

[0298] Mg: 0-0.010%, and

[0299] Rare earth elements: one or more elements selected from the group consisting of 0 to 0.100% are substituted for a portion of Fe.

[0300] These optional elements are described below.

[0301] [For Group 1: B, Cu, W and Co]

[0302] Alternatively, the chemical composition of the base material 10 of the present embodiment may further contain one or more elements selected from the group consisting of B, Cu, W, and Co to replace a portion of Fe. These elements are all arbitrary elements and may not be contained. When contained, the elements of B, Cu, W, and Co all increase the high temperature strength of the base material 10.

[0303] B: 0~0.0080%

[0304] Boron (B) is an arbitrary element and may not be contained. That is, B may also be 0%. When B is contained, that is, when the B content is greater than 0%, B segregates at the grain boundaries during use in a high-temperature corrosion environment of 600 to 700°C, thereby increasing the grain boundary strength. As a result, the high-temperature strength of the base material 10 is increased in a high-temperature corrosion environment of 600 to 700°C. As long as a small amount of B is contained, the above-mentioned effect can be obtained to some extent. On the other hand, if the B content is greater than 0.0080%, the B content of the weld metal will be increased during welding, and the weld hot cracking resistance of the weld metal 20 will be reduced. Therefore, the B content is 0 to 0.0080%.

[0305] The lower limit of the B content is preferably 0.0001%, more preferably 0.0005%, more preferably 0.0010%, more preferably 0.0015%, more preferably 0.0018%, more preferably 0.0020%, and still more preferably 0.0022%.

[0306] The upper limit of the B content is preferably less than 0.0060%, more preferably 0.0050%, and further preferably 0.0040%.

[0307] Cu: 0~5.00%

[0308] Copper (Cu) is an arbitrary element and may not be contained. That is, Cu may also be 0%. When Cu is contained, that is, when the Cu content is greater than 0%, Cu precipitates as a Cu phase in the grains during use in a high-temperature corrosive environment of 600 to 700°C, thereby improving the high-temperature strength of the base material 10 due to precipitation strengthening. As long as a small amount of Cu is contained, the above-mentioned effect can be obtained to some extent. However, if the Cu content is greater than 5.00%, the hot workability and weldability of the alloy are reduced. Therefore, the Cu content is 0 to 5.00%.

[0309] The lower limit of the Cu content is preferably 0.01%, more preferably 0.05%, more preferably 0.10%, more preferably 0.50%, more preferably 1.00%, more preferably 2.00%, and more preferably 2.50%.

[0310] The preferred upper limit of the Cu content is 4.50%, more preferably 4.00%, more preferably 3.80%, more preferably 3.70%, more preferably 3.60%, more preferably 3.50%, and more preferably 3.00%.

[0311] W: 0~5.00%

[0312] Tungsten (W) is an arbitrary element and may not be contained. That is, W may also be 0%. When W is contained, that is, when the W content is greater than 0%, W is solid-dissolved in the matrix (parent phase) and improves the high-temperature strength of the base material 10 of the austenitic stainless steel alloy weld joint 1. As long as a small amount of W is contained, the above-mentioned effect can be obtained to some extent. However, if the W content is greater than 5.00%, the stability of austenite is reduced and the aging toughness of the base material 10 is reduced. Therefore, the W content is 0 to 5.00%.

[0313] The lower limit of the W content is preferably 0.01%, more preferably 0.02%, further preferably 0.05%, further preferably 0.10%.

[0314] The upper limit of the W content is preferably 4.50%, more preferably 4.00%, and further preferably 3.50%.

[0315] Co: 0~1.00%

[0316] Cobalt (Co) is an arbitrary element and may not be contained. That is, the Co content may be 0%. When Co is contained, that is, when the Co content is greater than 0%, Co stabilizes austenite and improves the high temperature strength of the base material 10 of the austenitic stainless steel alloy weld joint 1. As long as a small amount of Co is contained, the above-mentioned effect can be obtained to some extent. However, if the Co content is greater than 1.00%, the raw material cost increases. Therefore, the Co content is 0 to 1.00%.

[0317] The lower limit of the Co content is preferably 0.01%, more preferably 0.02%, further preferably 0.03%, further preferably 0.10%.

[0318] The upper limit of the Co content is preferably 0.90%, more preferably 0.80%, and further preferably 0.60%.

[0319] [For Group 2: V, Ta, and Hf]

[0320] The chemical composition of the base material 10 of the present embodiment may further contain one or more elements selected from the group consisting of V, Ta, and Hf to replace a portion of Fe. These elements are arbitrary elements and may not be contained. When contained, the elements of V, Ta, and Hf all improve the polythionic acid SCC resistance of the base material 10.

[0321] V: 0~1.00%

[0322] Vanadium (V) is an arbitrary element and may not be contained. That is, the V content may also be 0%. When V is contained, that is, when the V content is greater than 0%, V combines with C to form carbonitrides during use in a high-temperature corrosion environment of 600 to 700°C. As a result, the solid-solution C in the base material 10 is reduced, and the polythionic acid SCC resistance of the base material 10 is improved. As long as a small amount of V is contained, the above-mentioned effect can be obtained to some extent. However, if the V content is greater than 1.00%, δ ferrite is generated and the aging toughness of the base material 10 is reduced. Therefore, the V content is 0 to 1.00%.

[0323] The lower limit of the V content is preferably 0.01%, more preferably 0.05%, and further preferably 0.10%.

[0324] The upper limit of the V content is preferably 0.90%, more preferably 0.80%, more preferably 0.60%, more preferably 0.40%, and still more preferably 0.20%.

[0325] Ta: 0~0.20%

[0326] Tantalum (Ta) is an arbitrary element and may not be contained. That is, the Ta content may also be 0%. When Ta is contained, that is, when the Ta content is greater than 0%, Ta combines with C to form carbonitrides during use in a high-temperature corrosion environment of 600 to 700°C. As a result, the solid-solution C in the base material 10 is reduced, and the polythionic acid SCC resistance of the base material 10 is improved. As long as a small amount of Ta is contained, the above-mentioned effect can be obtained to some extent. However, if the Ta content is greater than 0.20%, δ ferrite is generated, and the aging toughness of the base material 10 is reduced. Therefore, the Ta content is 0 to 0.20%.

[0327] The lower limit of the Ta content is preferably 0.01%, more preferably 0.02%.

[0328] The upper limit of the Ta content is preferably 0.18%, more preferably 0.16%, and further preferably 0.14%.

[0329] Hf: 0~0.20%

[0330] Hafnium (Hf) is an arbitrary element and may not be contained. That is, the Hf content may also be 0%. When Hf is contained, that is, when the Hf content is greater than 0%, Hf combines with C to form carbonitrides during use in a high-temperature corrosion environment of 600 to 700°C. As a result, the solid-solution C in the base material 10 is reduced, and the polythionic acid SCC resistance of the base material 10 is improved. As long as a small amount of Hf is contained, the above-mentioned effect can be obtained to some extent. However, if the Hf content is greater than 0.20%, δ ferrite is generated, and the creep strength, toughness, and weldability of the base material 10 are reduced. Therefore, the Hf content is 0 to 0.20%.

[0331] The lower limit of the Hf content is preferably 0.01%, more preferably 0.02%.

[0332] The upper limit of the Hf content is preferably 0.18%, more preferably 0.16%, and further preferably 0.14%.

[0333] [For Group 3: Ca, Mg and rare earth elements]

[0334] Alternatively, the chemical composition of the base material 10 of the present embodiment may further contain one or more elements selected from the group consisting of Ca, Mg, and rare earth elements (REM) to replace a portion of Fe. These elements are all arbitrary elements and may not be contained. When contained, Ca, Mg, and rare earth elements all improve the hot workability of the base material.

[0335] Ca: 0~0.010%

[0336] Calcium (Ca) is an arbitrary element and may not be contained. That is, the Ca content may be 0%. When Ca is contained, that is, when the Ca content is greater than 0%, Ca fixes O (oxygen) and S (sulfur) as inclusions, thereby improving the hot workability of the base material 10. As long as a small amount of Ca is contained, the above-mentioned effect can be obtained to some extent. However, if the Ca content is greater than 0.010%, the hot workability and creep ductility of the base material 10 are reduced. Therefore, the Ca content is 0 to 0.010%.

[0337] The lower limit of the Ca content is preferably 0.001%, more preferably 0.002%.

[0338] The upper limit of the Ca content is preferably 0.008%, more preferably 0.006%, and further preferably 0.004%.

[0339] Mg: 0~0.010%

[0340] Magnesium (Mg) is an arbitrary element and may not be contained. That is, the Mg content may be 0%. When Mg is contained, that is, when the Mg content is greater than 0%, Mg fixes O (oxygen) and S (sulfur) as inclusions, thereby improving the hot workability of the base material 10. As long as a small amount of Mg is contained, the above-mentioned effect can be obtained to some extent. However, if the Mg content is greater than 0.010%, the hot workability and creep ductility of the base material 10 are reduced. Therefore, the Mg content is 0 to 0.010%.

[0341] The lower limit of the Mg content is preferably 0.001%, more preferably 0.002%.

[0342] The upper limit of the Mg content is preferably 0.008%, more preferably 0.006%, and further preferably 0.004%.

[0343] Rare earth elements: 0~0.100%

[0344] Rare earth elements (REM) are arbitrary elements and may not be contained. That is, the REM content may be 0%. When REM is contained, that is, when the REM content is greater than 0%, REM fixes O (oxygen) and S (sulfur) as inclusions, thereby improving the hot workability of the base material. As long as a small amount of REM is contained, the above-mentioned effects can be obtained to some extent. However, if the REM content is greater than 0.100%, the hot workability and creep ductility of the base material are reduced. Therefore, the REM content is 0 to 0.100%.

[0345] The lower limit of the REM content is preferably 0.001%, more preferably 0.002%.

[0346] The upper limit of the REM content is preferably 0.080%, more preferably 0.060%.

[0347] The REM in this specification contains at least one or more of Sc, Y, and lanthanoid elements (La with atomic numbers 57 to Lu with atomic numbers 71), and the REM content means the total content of these elements.

[0348] [Regarding (Feature 2) Chemical Composition of Weld Metal 20]

[0349] Figure 5 1 is a cross-sectional view perpendicular to the weld metal extending direction L of the austenitic stainless steel alloy weld joint 1 according to the present embodiment. Figure 5 In the cross section of the weld metal 20 perpendicular to the weld metal extending direction L, the width at the surface of the weld metal 20 is defined as w (mm). And the thickness of the weld metal 20 at the center of the width w is defined as t (mm). At this time, the center of the width of the weld metal 20 and the center of the thickness of the weld metal 20 (that is, the depth t / 2 from the surface of the weld metal 20) is defined as region P. The chemical composition of region P is defined as the chemical composition of the weld metal 20. The chemical composition of the weld metal 20 contains the following elements.

[0350] C: 0.020% or less

[0351] It is inevitable to contain carbon (C). That is, the C content is greater than 0%. When used in a high temperature corrosive environment of 600 to 700°C, Cr carbides (M 23 C 6 Type carbide). Due to the formation of Cr carbides, the solid solution Cr is reduced. Therefore, the polythionic acid SCC resistance of the weld metal 20 is reduced. Therefore, the C content is 0.020% or less.

[0352] The C content is preferably as low as possible. However, excessive reduction of the C content will increase the production cost. Therefore, in industrial production, the preferred lower limit of the C content is 0.001%, and more preferably 0.005%.

[0353] The upper limit of the C content is preferably 0.019%, more preferably 0.018%, further preferably 0.017%, further preferably 0.015%.

[0354] Si: 0.01~1.00%

[0355] Silicon (Si) deoxidizes the weld metal 20 during welding. If the Si content is less than 0.01%, the above-mentioned effects cannot be fully obtained even if the contents of other elements are within the range of the present embodiment. On the other hand, if the Si content exceeds 1.00%, the aging toughness of the weld metal 20 decreases. Therefore, the Si content is 0.01 to 1.00%.

[0356] The lower limit of the Si content is preferably 0.02%, more preferably 0.03%, further preferably 0.05%, further preferably 0.10%.

[0357] The upper limit of the Si content is preferably 0.95%, more preferably 0.90%, more preferably 0.80%, more preferably 0.76%, more preferably 0.65%, more preferably 0.40%, and more preferably 0.35%.

[0358] Mn: 0.20~2.00%

[0359] Manganese (Mn) deoxidizes the weld metal 20 during welding. If the Mn content is less than 0.20%, the above-mentioned effects cannot be fully obtained even if the contents of other elements are within the range of the present embodiment. On the other hand, if the Mn content exceeds 2.00%, the high temperature strength of the weld metal 20 decreases. Therefore, the Mn content is 0.20 to 2.00%.

[0360] The lower limit of the Mn content is preferably 0.25%, more preferably 0.28%, more preferably 0.30%, more preferably 0.35%, and still more preferably 0.40%.

[0361] The upper limit of the Mn content is preferably 1.90%, more preferably 1.85%, more preferably 1.80%, more preferably 1.75%, more preferably 1.70%, more preferably 1.50%, and more preferably 1.30%.

[0362] P: 0.030% or less

[0363] Phosphorus (P) is an impurity that is inevitably contained. That is, the P content is greater than 0%. If the P content is greater than 0.030%, the welding hot cracking resistance of the weld metal 20 will decrease even if the contents of other elements are within the range of the present embodiment. Therefore, the P content is 0.030% or less.

[0364] The P content is preferably as low as possible. However, excessive reduction of the P content will increase the manufacturing cost. Therefore, in industrial production, the preferred lower limit of the P content is 0.001%, more preferably 0.002%, and even more preferably 0.003%.

[0365] The upper limit of the P content is preferably 0.025%, more preferably 0.020%.

[0366] S: 0.010% or less

[0367] Sulfur (S) is an impurity that is inevitably contained. That is, the S content is greater than 0%. If the S content is greater than 0.010%, the welding hot cracking resistance of the weld metal 20 will be reduced even if the contents of other elements are within the range of the present embodiment. Therefore, the S content is 0.010% or less.

[0368] The S content is preferably as low as possible. However, excessive reduction of the S content will increase the manufacturing cost. Therefore, in industrial production, the preferred lower limit of the S content is 0.001%, and more preferably 0.002%.

[0369] The upper limit of the S content is preferably 0.009%, more preferably 0.007%.

[0370] Cr: 16.0~25.0%

[0371] Chromium (Cr) improves the polythionic acid SCC resistance of the weld metal 20. If the Cr content is less than 16.0%, the above-mentioned effect cannot be fully obtained even if the contents of other elements are within the range of the present embodiment. On the other hand, if the Cr content exceeds 25.0%, the aging toughness of the weld metal 20 decreases. Therefore, the Cr content is 16.0 to 25.0%.

[0372] The lower limit of the Cr content is preferably 16.5%, more preferably 17.0%.

[0373] The upper limit of the Cr content is preferably 24.5%, more preferably 24.0%, further preferably 23.5%, further preferably 23.0%.

[0374] Ni: 15.0~40.0%

[0375] Nickel (Ni) stabilizes austenite and improves the aging toughness of the weld metal 20. If the Ni content is less than 15.0%, the above effects cannot be fully obtained even if the contents of other elements are within the range of the present embodiment. On the other hand, if the Ni content exceeds 40.0%, the above effects are saturated and the manufacturing cost becomes high. Therefore, the Ni content is 15.0 to 40.0%.

[0376] The preferred lower limit of the Ni content is 15.5%, more preferably 16.0%, more preferably 17.0%, more preferably 18.0%, and still more preferably 19.0%.

[0377] The upper limit of the Ni content is preferably 39.0%, more preferably 38.0%, more preferably 36.5%, more preferably 35.0%, and still more preferably 33.0%.

[0378] Mo: 2.5~5.0%

[0379] Molybdenum (Mo) suppresses the formation of Cr carbides (M 23 C 6 type carbide). Thus, the polythionic acid SCC resistance of the weld metal 20 is improved. With regard to Mo, during the use of the weld joint in a high-temperature corrosive environment, the solid-solution Mo in the weld metal 20 combines with S in the use environment to form a sulfide film on the surface of the weld metal 20. Due to the formation of this sulfide film, the cyclohexane acid corrosion resistance of the weld metal 20 is improved. If the Mo content is less than 2.5%, even if the contents of other elements are within the range of the present embodiment, the above-mentioned effects cannot be fully obtained. On the other hand, if the Mo content is greater than 5.0%, sufficient aging toughness cannot be obtained. Therefore, the Mo content is 2.5 to 5.0%.

[0380] The lower limit of the Mo content is preferably 2.6%, more preferably 2.7%, and further preferably 2.8%.

[0381] The upper limit of the Mo content is preferably 4.5%, more preferably 4.0%.

[0382] Nb: 0.10~2.00%

[0383] Niobium (Nb) combines with C to form MX-type carbonitrides during use in a high-temperature corrosive environment of 600 to 700°C, thereby reducing the amount of solid-solution C in the weld metal 20. As a result, the polythionic acid SCC resistance of the weld metal 20 is improved. In addition, the generated MX-type carbonitrides of Nb also improve the creep strength. If the Nb content is less than 0.10%, even if the contents of other elements are within the range of the present embodiment, the above effects cannot be fully obtained. On the other hand, if the Nb content is more than 2.00%, δ-ferrite is generated, and the long-term creep strength, toughness, and weldability of the weld metal 20 are reduced. Therefore, the Nb content is 0.10 to 2.00%.

[0384] The lower limit of the Nb content is preferably 0.11%, more preferably 0.12%, further preferably 0.15%, further preferably 0.20%.

[0385] The upper limit of the Nb content is preferably 1.90%, more preferably 1.80%, more preferably 1.40%, more preferably 1.00%, more preferably 0.75%, more preferably 0.70%, and more preferably 0.65%.

[0386] N: 0.05~0.30%

[0387] Nitrogen (N) is dissolved in the matrix (parent phase) to stabilize austenite and improve the high temperature strength of the weld metal 20. N also forms fine carbonitrides in the grains to improve the high temperature strength of the weld metal 20. If the N content is less than 0.05%, even if the contents of other elements are within the range of the present embodiment, the above effects cannot be fully obtained. On the other hand, if the N content exceeds 0.30%, Cr nitrides are formed at the grain boundaries, and the polythionic acid SCC resistance and naphthenic acid corrosion resistance in the weld metal 20 are reduced. Therefore, the N content is 0.05 to 0.30%.

[0388] The lower limit of the N content is preferably 0.06%, more preferably 0.07%, further preferably 0.08%, further preferably 0.10%.

[0389] The upper limit of the N content is preferably 0.28%, more preferably 0.25%.

[0390] Sol.Al: 0.001~0.100%

[0391] Aluminum (Al) deoxidizes the weld metal 20 during welding. If the Al content is less than 0.001%, the above-mentioned effects cannot be fully obtained even if the contents of other elements are within the range of the present embodiment. On the other hand, if the Al content exceeds 0.100%, the ductility of the weld metal 20 decreases. Therefore, the Al content is 0.001 to 0.100%.

[0392] The lower limit of the Al content is preferably 0.002%, more preferably 0.010%.

[0393] The upper limit of the Al content is preferably 0.085%, more preferably 0.080%, more preferably 0.060%, more preferably 0.040%, more preferably 0.030%, more preferably 0.025%, and more preferably 0.020%.

[0394] In the present embodiment, the Al content refers to the content of acid-soluble Al (sol. Al).

[0395] B: 0.0010~0.0050%

[0396] Boron (B) segregates at the grain boundaries during use in a high-temperature corrosive environment of 600 to 700°C, thereby increasing the grain boundary strength. As a result, the high-temperature strength of the weld metal 20 is increased in a high-temperature corrosive environment of 600 to 700°C. If the B content is less than 0.0010%, even if the contents of other elements are within the range of the present embodiment, the above-mentioned effects cannot be fully obtained. On the other hand, if the B content exceeds 0.0050%, the weld hot cracking resistance of the weld metal 20 decreases. Therefore, the B content is 0.0010 to 0.0050%.

[0397] The lower limit of the B content is preferably 0.0011%, more preferably 0.0012%, more preferably 0.0015%, more preferably 0.0020%, and more preferably 0.0030%. When the B content in the weld metal 20 is 0.0030% or more, excellent creep strength can be obtained in the weld joint 1.

[0398] The upper limit of the B content is preferably 0.0045%, more preferably 0.0040%, and further preferably 0.0035%.

[0399] The balance of the chemical composition of the weld metal 20 of the austenitic stainless steel alloy weld joint 1 of the present embodiment is Fe and impurities. Here, impurities refer to elements mixed from the welding material as a raw material and the environment during welding when forming the weld metal 20, and are not intentionally contained elements, but are allowed elements within a range that does not adversely affect the weld metal 20.

[0400] [Optional Elements]

[0401] The chemical composition of the weld metal 20 of the austenitic stainless steel alloy weld joint 1 of the present embodiment further includes a

[0402] Cu: 0-5.00%,

[0403] W: 0~5.00%,

[0404] Co: 0-1.00%,

[0405] V: 0~1.00%,

[0406] Ta: 0~0.20%,

[0407] Hf: 0~0.20%,

[0408] Ca: 0~0.010%

[0409] Mg: 0-0.010%, and

[0410] Rare earth elements: one or more elements selected from the group consisting of 0 to 0.100% are substituted for a portion of Fe.

[0411] These optional elements are described below.

[0412] [For Group 1: Cu, W and Co]

[0413] The chemical composition of the weld metal 20 of the present embodiment may further contain one or more elements selected from the group consisting of Cu, W, and Co in place of a portion of Fe. These elements all increase the creep strength of the weld metal 20 .

[0414] Cu: 0~5.00%

[0415] Copper (Cu) is an arbitrary element and may not be contained. That is, Cu may be 0%. When Cu is contained, that is, when the Cu content is greater than 0%, Cu precipitates as a Cu phase in the grains during use in a high-temperature corrosive environment of 600 to 700°C, and the high-temperature strength of the weld metal 20 is improved due to precipitation strengthening. As long as a small amount of Cu is contained, the above-mentioned effect can be obtained to some extent. However, if the Cu content is greater than 5.00%, the weldability of the alloy decreases. Therefore, the Cu content is 0 to 5.00%.

[0416] The lower limit of the Cu content is preferably 0.01%, more preferably 0.05%, more preferably 0.10%, more preferably 0.50%, more preferably 1.00%, more preferably 2.00%, and more preferably 2.50%.

[0417] The preferred upper limit of the Cu content is 4.50%, more preferably 4.00%, more preferably 3.80%, more preferably 3.70%, more preferably 3.60%, more preferably 3.50%, and more preferably 1.90%.

[0418] W: 0~5.00%

[0419] Tungsten (W) is an arbitrary element and may not be contained. That is, W may be 0%. When W is contained, that is, when the W content is greater than 0%, W is solid-dissolved in the matrix (parent phase) and improves the high-temperature strength of the weld metal 20. As long as a small amount of W is contained, the above-mentioned effect can be obtained to some extent. However, if the W content is greater than 5.00%, the stability of austenite decreases and the aging toughness of the weld metal 20 decreases. Therefore, the W content is 0 to 5.00%.

[0420] The lower limit of the W content is preferably 0.01%, more preferably 0.02%, further preferably 0.05%, further preferably 0.10%.

[0421] The upper limit of the W content is preferably 4.50%, more preferably 4.00%, further preferably 3.80%, further preferably 3.50%.

[0422] Co: 0~1.00%

[0423] Cobalt (Co) is an arbitrary element and may not be contained. That is, the Co content may be 0%. When Co is contained, that is, when the Co content is greater than 0%, Co stabilizes austenite and improves the high temperature strength of the weld metal 20. As long as a small amount of Co is contained, the above effect can be obtained to some extent. However, if the Co content is greater than 1.00%, the raw material cost increases. Therefore, the Co content is 0 to 1.00%.

[0424] The lower limit of the Co content is preferably 0.01%, more preferably 0.02%, further preferably 0.03%, further preferably 0.10%.

[0425] The upper limit of the Co content is preferably 0.90%, more preferably 0.80%, more preferably 0.60%, more preferably 0.50%, and still more preferably 0.45%.

[0426] [For Group 2: V, Ta, and Hf]

[0427] The chemical composition of the weld metal 20 of the present embodiment may further contain one or more elements selected from the group consisting of V, Ta, and Hf to replace a portion of Fe. These elements are arbitrary elements and may not be contained. When contained, the elements of V, Ta, and Hf all improve the polythionic acid SCC resistance of the weld metal 20.

[0428] V: 0~1.00%

[0429] Vanadium (V) is an arbitrary element and may not be contained. That is, the V content may also be 0%. When V is contained, that is, when the V content is greater than 0%, V combines with C to form carbonitrides during use in a high-temperature corrosion environment of 600 to 700°C. As a result, the solid solution C in the weld metal 20 is reduced, and the polythionic acid SCC resistance of the weld metal 20 is improved. As long as a small amount of V is contained, the above effect can be obtained to some extent. However, if the V content is greater than 1.00%, δ ferrite is generated and the aging toughness of the weld metal 20 is reduced. Therefore, the V content is 0 to 1.00%.

[0430] The lower limit of the V content is preferably 0.01%, more preferably 0.05%, and further preferably 0.10%.

[0431] The upper limit of the V content is preferably 0.90%, more preferably 0.80%, more preferably 0.60%, more preferably 0.40%, more preferably 0.20%, more preferably 0.15%, and more preferably 0.10%.

[0432] Ta: 0~0.20%

[0433] Tantalum (Ta) is an arbitrary element and may not be contained. That is, the Ta content may also be 0%. When Ta is contained, that is, when the Ta content is greater than 0%, Ta combines with C to form carbonitrides during use in a high-temperature corrosive environment of 600 to 700°C. As a result, the solid-solution C in the weld metal 20 is reduced, and the polythionic acid SCC resistance of the weld metal 20 is improved. As long as a small amount of Ta is contained, the above-mentioned effect can be obtained to some extent. However, if the Ta content is greater than 0.20%, δ ferrite is generated, and the aging toughness of the weld metal 20 is reduced. Therefore, the Ta content is 0 to 0.20%.

[0434] The lower limit of the Ta content for further effectively improving the polythionic acid SCC resistance is preferably 0.01%, and more preferably 0.02%.

[0435] The upper limit of the Ta content is preferably 0.18%, more preferably 0.16%, and further preferably 0.14%.

[0436] Hf: 0~0.20%

[0437] Hafnium (Hf) is an arbitrary element and may not be contained. That is, the Hf content may also be 0%. When Hf is contained, that is, when the Hf content is greater than 0%, Hf combines with C to form carbonitrides during use in a high-temperature corrosive environment of 600 to 700°C. As a result, the solid-solution C in the weld metal 20 is reduced, and the polythionic acid SCC resistance of the weld metal 20 is improved. As long as a small amount of Hf is contained, the above-mentioned effect can be obtained to some extent. However, if the Hf content is greater than 0.20%, δ ferrite is generated, and the creep strength, toughness, and weldability of the weld metal 20 are reduced. Therefore, the Hf content is 0 to 0.20%.

[0438] The lower limit of the Hf content is preferably 0.01%, more preferably 0.02%.

[0439] The upper limit of the Hf content is preferably 0.18%, more preferably 0.16%, and further preferably 0.14%.

[0440] [For Group 3: Ca, Mg and rare earth elements]

[0441] The chemical composition of the weld metal 20 of the present embodiment may further contain one or more elements selected from the group consisting of Ca, Mg, and rare earth elements to replace a portion of Fe. These elements are arbitrary elements and may not be contained. When contained, Ca, Mg, and rare earth elements all improve the ductility of the weld metal 20.

[0442] Ca: 0~0.010%

[0443] Calcium (Ca) is an arbitrary element and may not be contained. That is, the Ca content may be 0%. When Ca is contained, that is, when the Ca content is greater than 0%, Ca fixes O (oxygen) and S (sulfur) as inclusions, thereby improving the ductility of the weld metal 20. As long as a small amount of Ca is contained, the above effect can be obtained to some extent. However, if the Ca content exceeds 0.010%, the ductility of the weld metal 20 decreases. Therefore, the Ca content is 0 to 0.010%.

[0444] The lower limit of the Ca content is preferably greater than 0%, more preferably 0.001%, and even more preferably 0.002%.

[0445] The upper limit of the Ca content is preferably 0.008%, more preferably 0.006%, and further preferably 0.004%.

[0446] Mg: 0~0.010%

[0447] Magnesium (Mg) is an arbitrary element and may not be contained. That is, the Mg content may be 0%. When Mg is contained, that is, when the Mg content is greater than 0%, Mg fixes O (oxygen) and S (sulfur) as inclusions, thereby improving the ductility of the weld metal 20. As long as a small amount of Mg is contained, the above-mentioned effect can be obtained to some extent. However, if the Mg content is greater than 0.010%, the ductility of the weld metal 20 decreases. Therefore, the Mg content is 0 to 0.010%.

[0448] The lower limit of the Mg content is preferably greater than 0%, more preferably 0.001%, and further preferably 0.002%.

[0449] The upper limit of the Mg content is preferably 0.008%, more preferably 0.006%, and further preferably 0.004%.

[0450] Rare earth elements: 0~0.100%

[0451] Rare earth elements (REM) are arbitrary elements and may not be contained. That is, the REM content may be 0%. When REM is contained, that is, when the REM content is greater than 0%, REM fixes O (oxygen) and S (sulfur) as inclusions, thereby improving the ductility of the weld metal 20. As long as a small amount of REM is contained, the above-mentioned effect can be obtained to some extent. However, if the REM content is greater than 0.100%, the ductility of the weld metal 20 decreases. Therefore, the REM content is 0 to 0.100%.

[0452] The lower limit of the REM content is preferably more than 0%, more preferably 0.001%, and even more preferably 0.002%.

[0453] The upper limit of the REM content is preferably 0.080%, more preferably 0.060%.

[0454] [For (Feature 3) F1 in weld metal 20]

[0455] Furthermore, in the weld metal 20, F1 defined by the formula (1) is 2.30 or less.

[0456] F1=130B+8C+0.025Cr+0.25Mn+0.08Mo+0.6Nb+12P+7.6S+0.78Si+0.012W(1)

[0457] In the formula (1), the content (mass %) of the corresponding element is substituted for each element symbol.

[0458] F1 is an index related to the hot cracking resistance of the weld metal 20. B, C, Cr, Mn, Mo, Nb, P, S, Si, and W are all elements that promote hot cracking during welding. If F1 composed of the contents of these elements is greater than 2.30, even if other characteristics 1, 2, and 4 are satisfied, the hot cracking resistance of the weld metal 20 during welding will be reduced.

[0459] If F1 is 2.30 or less, sufficient resistance to welding hot cracking can be obtained in the weld metal 20 on the premise of satisfying the other characteristics 1, 2, and 4. Therefore, F1 is 2.30 or less.

[0460] The preferred upper limit of F1 is 2.28, more preferably 2.25, more preferably 2.22, more preferably 2.20, more preferably 2.18, more preferably 2.15, more preferably 2.10, and more preferably 2.05. In addition, F1 is a value obtained by rounding off the third decimal place of the obtained value (the value of the second decimal place).

[0461] [For (Feature 4) F2 in weld metal 20]

[0462] In a cross section of the weld metal perpendicular to the extending direction of the weld metal 20, a 1 mm × 1 mm square area at the center of the width of the surface of the weld metal and at the center of the thickness of the weld metal is divided into small square areas of 100 μm × 100 μm, and the Mo content in mass % in each small square area is calculated. The arithmetic mean of all the Mo contents obtained is defined as [Mo] AVE , the total Mo content obtained is [Mo] AVE The arithmetic mean of the high Mo content is defined as [Mo] H , the total Mo content obtained is [Mo] AVE The arithmetic mean of the low Mo content is defined as [Mo] L When F2 defined by formula (2) is less than 2.5.

[0463] F2=[Mo] H / [Mo] L (2)

[0464] F2 is an index related to the Mo segregation degree in the square region of the weld metal 20. In the austenitic stainless steel alloy weld joint 1 of the present embodiment, the Mo content is high in order to improve the naphthenic acid corrosion resistance. Although Mo improves the naphthenic acid corrosion resistance, it is easy to segregate at the grain boundary.

[0465] [Mo] HRefers to the average Mo content ratio in the square area [Mo] AVE Mo content in the high region. That is, [Mo] H It is an indicator of the Mo content of segregation. On the other hand, [Mo] L Refers to the average Mo content ratio in the square area [Mo] AVE The Mo content in the low region. That is, [Mo] L It is an indicator of the Mo content in regions other than the region where Mo segregates.

[0466] If F2 increases, the segregation degree of Mo in the square region is high. In other words, it is considered that the Mo segregation degree at the grain boundary is high. In this case, the Mo concentration at the grain boundary is high, and the Mo concentration in the grain becomes low. Therefore, the strength of the grain boundary becomes excessively high compared to the strength in the grain. In other words, the difference between the grain boundary strength and the strength in the grain in the weld metal 20 becomes large. As a result, the naphthenic acid corrosion resistance and aging toughness cannot be fully obtained.

[0467] When F2 is 2.5 or less, the segregation degree of Mo in the square region is sufficiently suppressed. Therefore, the difference between the grain boundary strength and the intragranular strength in the weld metal 20 becomes small. As a result, sufficient naphthenic acid corrosion resistance and sufficient aging toughness can be obtained.

[0468] The preferred upper limit of F2 is 2.4, more preferably 2.3, more preferably 2.2, more preferably 2.1, more preferably 2.0, more preferably 1.8, more preferably 1.6, and more preferably 1.4.

[0469] [F2 measurement method]

[0470] F2 can be measured by the following method.

[0471] Reference Figure 5, in the cross section of the weld metal 20 perpendicular to the weld metal extension direction L, determine the area P which is the central part of the width at the surface of the weld metal 20 and the central part of the thickness of the weld metal 20. Moreover, in the area P, a test piece having a surface (observation surface) including a square area of ​​1mm×1mm is collected. The observation surface of the test piece is mirror-polished. Select an arbitrary square area from the observation surface after mirror polishing. The selected square area is subjected to surface analysis using a field emission electron probe microanalyzer (FE-EPMA). Specifically, the square area is divided into small square areas of 100μm×100μm. And, elemental analysis is performed on each small square. The acceleration voltage is set to 15kV, the irradiation current is set to 400nA, the beam diameter is set to 2μm, and the cumulative time is set to 0.1 second. The element to be measured is set to Mo, and the Mo content in mass % in each small square area is calculated. The arithmetic mean of all the Mo contents (mass %) obtained is defined as [Mo] AVE .

[0472] The total Mo content measured was divided into [Mo] AVE Small square areas with high Mo content and ratio [Mo] AVE Small square areas with low Mo content. Excludes [Mo] AVE Tiny square areas with the same Mo content.

[0473] Compared with [Mo] AVE The arithmetic mean value of the Mo content in the tiny square area with high Mo content is defined as [Mo] H . Compared with [Mo] AVE The arithmetic mean of the Mo content in the small square area with low Mo content is defined as [Mo] L Based on the obtained [Mo] H and [Mo] L , use formula (2) to calculate F2.

[0474] [Regarding the Austenitic Stainless Steel Alloy Welding Material of the Present Embodiment]

[0475] As a welding material for the weld metal 20 of the austenitic stainless steel alloy weld joint 1 of the present embodiment, a chemical composition of C: 0.020% or less, Si: 0.01 to 1.00%, Mn: 0.20 to 2.00%, P: 0.030% or less, S: 0.010% or less, Cr: 16.0 to 25.0%, Ni: 15.0 to 40.0%, Mo: 2.5 to 5.0%, Nb: 0.10 to 2.00%, N: 0.05 to 0.06% is used. .30%, sol.Al: 0.001-0.100%, B: 0.0010-0.0050%, Cu: 0-5.00%, W: 0-5.00%, Co: 0-1.00%, V: 0-1.00%, Ta: 0-0.20%, Hf: 0-0.20%, Ca: 0-0.010%, Mg: 0-0.010%, rare earth element: 0-0.100%, and the balance is Fe and impurities, an austenitic stainless steel alloy welding material. The role, preferred lower limit, and preferred upper limit of each element in the chemical composition of the austenitic stainless steel alloy welding material are the same as the role, preferred lower limit, and preferred upper limit of each element in the chemical composition of the weld metal 20.

[0476] The weld metal 20 is formed by welding the austenitic stainless steel alloy welding material having the above chemical composition to the base material 10 by a welding method described below. If the chemical composition of the austenitic stainless steel alloy welding material is out of the above range, the weld metal 20 cannot be formed.

[0477] [Effects of Austenitic Stainless Steel Alloy Welded Joint 1]

[0478] The austenitic stainless steel alloy weld joint 1 of the present embodiment satisfies Features 1 to 4. Therefore, in the weld metal 20, sufficient welding hot cracking resistance, sufficient polythionic acid SCC resistance, sufficient naphthenic acid corrosion resistance, and sufficient aging toughness can be obtained.

[0479] [Manufacturing method]

[0480] An example of a method for manufacturing the austenitic stainless steel alloy welded joint 1 of the present embodiment is described. The method for manufacturing the austenitic stainless steel alloy welded joint 1 described below is an example for manufacturing the austenitic stainless steel alloy welded joint 1 of the present embodiment. Therefore, the austenitic stainless steel alloy welded joint 1 having the above-mentioned structure can also be manufactured by other manufacturing methods other than the manufacturing method described below. However, the manufacturing method described below is a preferred example of the method for manufacturing the austenitic stainless steel alloy welded joint 1 of the present embodiment.

[0481] An example of the production method includes the following steps.

[0482] (Process 1) Base material preparation process

[0483] (Process 2) Welding process

[0484] Hereinafter, steps 1 and 2 will be described.

[0485] [(Process 1) Base material preparation process]

[0486] In the base material preparation step, a base material 10 satisfying feature 1 is prepared. The shape of the base material 10 is not particularly limited. As described above, the base material 10 may be an alloy plate or an alloy tube. The base material 10 may be a bar or a steel section.

[0487] When manufacturing the base material 10 , the base material preparation step includes the following steps.

[0488] (Process 11) Preparation process

[0489] (Process 12) Hot working process

[0490] (Process 13) Cold working process

[0491] (Step 14) Solution Treatment Step

[0492] Hereinafter, step 11 to step 14 will be described.

[0493] [(Step 11) Preparation Step]

[0494] A molten alloy satisfying feature 1 is manufactured. For example, the molten alloy is manufactured using an electric furnace, an AOD (argon oxygen decarburization: Argon Oxygen Decarburization) furnace, or a VOD (vacuum oxygen decarburization: Vacuum Oxygen Decarburization) furnace. The manufactured molten alloy is subjected to a well-known degassing treatment as required. A billet is manufactured from the molten alloy subjected to the degassing treatment. The billet is manufactured by, for example, a continuous casting method. A continuous casting material (bill) is manufactured by a continuous casting method. Continuous casting materials are, for example, slabs, blooms, and billets. The molten alloy may also be made into an ingot by an ingot casting method.

[0495] [(Step 12) Hot working step]

[0496] The prepared billet (continuous casting material or ingot) is subjected to hot working to manufacture the base material. For example, the billet is subjected to hot rolling to manufacture an alloy plate as the base material 10. In addition, the billet is subjected to hot extrusion, hot piercing rolling, etc. to manufacture an alloy tube as the base material 10. The specific method of hot working is not particularly limited, and hot working corresponding to the shape of the final product can be performed. The processing end temperature of the hot working is, for example, above 1000°C, and more preferably above 1050°C. The so-called processing end temperature here refers to the temperature of the base material 10 just after the final hot working is completed.

[0497] [(Process 13) Cold working process]

[0498] The base material after the hot working step may be subjected to cold working as required. When the base material 10 is an alloy tube, the cold working is, for example, cold drawing or cold rolling. When the base material 10 is an alloy plate, the cold working is, for example, cold rolling.

[0499] [(Step 14) Solution treatment step]

[0500] Alternatively, after the hot working step or after the cold working step, the base material 10 may be subjected to a solution treatment as required. In the solution treatment step, the structure is homogenized and the carbonitride is dissolved. The preferred solution treatment temperature is 1000 to 1250° C. The holding time of the above-mentioned solution treatment temperature is not particularly limited, and is, for example, 2 minutes to 60 minutes.

[0501] [(Process 2) Welding process]

[0502] The prepared base material 10 is welded to produce an austenitic stainless steel alloy welded joint 1. A groove is formed at the end of the base material 10. Two base materials 10 with grooves are prepared. The grooves of the prepared base materials 10 are butted against each other. Then, the butted pair of grooves are welded using an austenitic stainless steel alloy welding material having the above-mentioned chemical composition to form a weld metal 20 having the above-mentioned chemical composition.

[0503] In addition, the following method is used to manufacture austenitic stainless steel alloy welding materials. A molten alloy having the above-mentioned chemical composition is manufactured. For example, the above-mentioned molten alloy is manufactured using an electric furnace, an AOD furnace, or a VOD furnace. The manufactured molten alloy is subjected to a well-known degassing treatment as required. A billet (continuous casting material or ingot) is manufactured from the molten alloy subjected to the degassing treatment. The billet is subjected to a well-known hot working to manufacture a wire-shaped austenitic stainless steel alloy welding material.

[0504] Examples of welding methods for the base material 10 using an austenitic stainless steel alloy welding material include TIG welding (GTAW), shielded metal arc welding (SMAW), flux-cored arc welding (FCAW), gas metal arc welding (GMAW), and submerged arc welding (SAW).

[0505] In the welding process, when the base material 10 is an alloy plate, for example, a groove is formed on the end face or side face of the alloy plate. When the base material 10 is an alloy tube, a groove is formed on the tube end in the axial direction of the alloy tube. When the base material 10 is an alloy tube, for example, an austenitic stainless steel alloy welded joint 1 is formed by performing girth welding.

[0506] In the welding process, welding is performed so as to satisfy the following conditions.

[0507] (Condition 1) Heat input: 3.0 kJ / mm or less

[0508] (Condition 2) Interlayer temperature: 150°C or less

[0509] (Condition 3) When the cooling rate at 1300° C. during welding is CR (° C. / sec) and the welding speed is V (mm / sec), FA defined by the following equation is greater than 0.60.

[0510] FA=V-0.0056×(CR / V)

[0511] The interlayer temperature refers to the surface temperature (°C) of the welded layer immediately before the welding of the next layer is started in multilayer cladding. The interlayer temperature of 150°C or less means that the interlayer temperature of each layer after each layer is formed is 150°C or less. In other words, the interlayer temperature of condition 2 means that the highest temperature among one or more interlayer temperatures is 150°C or less.

[0512] FA is an index for suppressing Mo segregation. The greater the welding speed V is or the smaller the temperature gradient (=CR / V) in the extension direction of the weld metal 20 is, the more Mo segregation during solidification of the weld metal 20 can be suppressed. If FA is greater than 0.60, Mo segregation in the weld metal 20 can be sufficiently suppressed.

[0513] The cooling rate CR at 1300° C. can be measured as follows: During welding in the welding process, a thermocouple is inserted into the molten pool to obtain a cooling curve. The cooling rate CR (° C. / sec) at 1300° C. is determined from the obtained cooling curve.

[0514] In addition, in the case of automatic welding, the welding speed V (mm / sec) is determined by the setting of the moving speed of the welding torch of the welding device, and in the case of circumferential welding of alloy pipes, it is determined by the setting of the moving speed of the welding device or the positioner (rotating device).

[0515] If the above-mentioned conditions 1 to 3 are satisfied, the weld metal 20 satisfying the characteristics 2 to 4 can be formed.

[0516] The above manufacturing process can be used to manufacture an austenitic stainless steel alloy welded joint that satisfies characteristics 1 to 4. In addition, the manufacturing method of the austenitic stainless steel alloy welded joint 1 of the present embodiment is not limited to the above manufacturing method. If the austenitic stainless steel alloy welded joint 1 that satisfies characteristics 1 to 4 can be manufactured, it can be manufactured by other methods.

[0517] The effects of the austenitic stainless steel alloy welded joint of the present embodiment will be further specifically described below using examples. The conditions in the following examples are one condition example adopted to confirm the feasibility and effects of the austenitic stainless steel alloy welded joint of the present embodiment. Therefore, the austenitic stainless steel alloy welded joint of the present embodiment is not limited to this one condition example.

[0518] Example

[0519] [Manufacture of welded joints of austenitic stainless steel alloys]

[0520] [Manufacturing of base material]

[0521] Molten alloys for base materials having the chemical compositions shown in Tables 1-1 and 1-2 were produced.

[0522] [Table 1-1]

[0523] Table 1-1

[0524]

[0525] [Table 1-2]

[0526] Table 1-2

[0527]

[0528] Specifically, an ingot with an outer diameter of 120 mm and a weight of 30 kg was manufactured using a molten alloy. The ingot was hot forged to form an alloy plate with a thickness of 30 mm. Furthermore, hot rolling was performed to form an alloy plate with a thickness of 15 mm. The processing end temperature during hot rolling was above 1050°C. The hot-rolled alloy plate was solution treated. In any alloy plate, the solution treatment temperature was 1150°C, and the solution treatment time was 10 minutes. The base material after the solution treatment was water-cooled. The above manufacturing process was used to manufacture an alloy plate (base material) with a thickness of 15 mm, a width of 50 mm, and a length of 100 mm.

[0529] [Manufacture of welding materials]

[0530] Welding materials having the chemical compositions shown in Table 2-1 and Table 2-2 were prepared. In the chemical composition of each welding material number, the balance other than the elements shown in Table 2-1 and Table 2-2 was Fe and impurities.

[0531] [Table 2-1]

[0532] Table 2-1

[0533]

[0534] [Table 2-2]

[0535] Table 2-2

[0536]

[0537] The molten alloy was used to produce an ingot with an outer diameter of 120 mm and a weight of 30 kg. The ingot was subjected to hot forging, hot rolling, cold rolling, and heat treatment by a well-known method to produce a welding wire (austenitic stainless steel alloy welding material) with an outer diameter of 1.2 mm.

[0538] [Manufacture of welded joints of austenitic stainless steel alloys]

[0539] Austenitic stainless steel alloy welded joints were manufactured by the following manufacturing method using the base materials in Tables 1-1 and 1-2 and the welding materials in Tables 2-1 and 2-2.

[0540] As the base material of Table 1-1 and Table 1-2, two Figure 6 Alloy plate shown. Figure 6 In the figure, the numerical value attached with "mm" indicates the size (in mm) of the alloy plate as the base material. The alloy plate has a groove surface on the side extending along the length direction. The groove surface is set as a V groove surface with a groove angle of 30° and a weld root thickness of 1 mm.

[0541] like Figure 7 As shown in FIG. 1 , a restraining plate 30 was prepared. The restraining plate 30 used was a member having a thickness of 25 mm, a width of 200 mm, and a length of 200 mm and having a chemical composition corresponding to "SM400C" described in JIS G 3106 (2008).

[0542] Two base materials (plate materials) 10 are placed on the restraining plate 30. At this time, the groove surfaces of the two base materials 10 are butted against each other. After the two base materials 10 are placed, restraint welding is performed around the base materials 10 using a shielded metal arc welding rod. The shielded metal arc welding rod uses an arc welding rod having a chemical composition equivalent to "ENiCrMo-3" specified in JIS Z 3224 (2010).

[0543] After restraint welding was performed on all sides of the base material 10, multilayer cladding by TIG welding (GTAW) was performed using the welding materials in Tables 2-1 and 2-2 to form weld metal. In each test number, the heat input (kJ / mm) during welding, the highest temperature (°C) of the interlayer temperature at each layer in the multilayer cladding, the welding speed V (°C / second), the cooling rate CR (mm / second) at 1300°C, and FA are as shown in the "Heat Input (kJ / mm)" column, the "Interlayer Temperature (°C)" column, the "Welding Speed ​​V (mm / second)" column, the "Cooling Rate CR (°C / second)" column, and the "FA" column in the "Welding Conditions" column of Table 4. Austenitic stainless steel alloy welded joints of each weld metal number were manufactured using the above manufacturing process.

[0544] [Analysis of chemical composition of weld metal]

[0545] The chemical composition of the austenitic stainless steel alloy welded joint of each weld metal number at the center of the width and the center of the thickness was measured using the well-known component analysis method according to JIS G 0321: 2017. Specifically, chips were collected from the area P at the center of the width of the weld metal and the center of the thickness of the weld metal using a drill. The collected chips were dissolved in acid to obtain a solution. The solution was subjected to ICP-AES (Inductively Coupled Plasma Atomic Emission Spectrometry) to perform elemental analysis of the chemical composition. For the C content and S content, the well-known high-frequency combustion method (combustion-infrared absorption method) was used to obtain them. For the N content and O content, the well-known inert gas melting-thermal conductivity method was used to obtain them.

[0546] The chemical compositions of the obtained weld metals are shown in Tables 3-1 and 3-2.

[0547] [Table 3-1]

[0548] Table 3-1

[0549]

[0550] [Table 3-2]

[0551] Table 3-2

[0552]

[0553] [Evaluation test]

[0554] The following tests were carried out on the manufactured austenitic stainless steel alloy welded joints.

[0555] (Test 1) F2 measurement test

[0556] (Test 2) Welding hot crack resistance evaluation test

[0557] (Test 3) Polythionic acid SCC resistance evaluation test

[0558] (Test 4) Naphthenic Acid Corrosion Resistance Evaluation Test

[0559] (Test 5) Aging toughness evaluation test

[0560] Hereinafter, Tests 1 to 5 will be described.

[0561] [(Test 1) F2 measurement test]

[0562] The F2 in the weld metal of each test number was determined based on the method described in the above-mentioned [F2 measurement method]. The obtained F2 values ​​are shown in Table 4.

[0563] [Table 4]

[0564] Table 4

[0565]

[0566] [(Test 2) Welding hot crack resistance evaluation test]

[0567] The following method was used to evaluate the hot cracking resistance of the austenitic stainless steel alloy welded joints of each weld metal number. Ten microstructure observation test pieces of cross sections orthogonal to the weld were collected from the weld metal of the austenitic stainless steel alloy welded joints of each weld metal number. The size of the test piece was set to 15 mm × 30 mm × 10 mm. The surface of the collected test piece corresponding to the cross section orthogonal to the weld was set as the "observation surface". The observation surface was 15 × 30 mm. The observation surface was mirror polished and etched with mixed acid. The surface of the etched test piece was observed using an optical microscope at 200 times. In addition, it was visually determined whether hot cracks were generated in the weld metal of the observation surface. The evaluation results are shown in Table 4. In the case where no cracks were confirmed in the weld metal in any of the 10 test pieces collected, it was judged that sufficient hot cracking resistance was obtained (in Table 4, "E (Excellent)"). On the other hand, when cracks were confirmed in even one of the 10 test pieces, it was determined that sufficient resistance to hot cracking during welding could not be obtained ("NA (Not Accepted)" in Table 4). In addition, for the test number determined as "NA" in the hot cracking resistance evaluation test, the test after test 3 was not performed.

[0568] [(Test 3) Polythionic acid SCC resistance evaluation test]

[0569] The polythionic acid SCC resistance of the weld metal of the austenitic stainless steel alloy weld joint having each weld metal number was evaluated by the following method.

[0570] First, aging treatment was performed on the austenitic stainless steel alloy welded joints of each weld metal number at 650°C for 3000 hours, assuming use in a high temperature environment. Figure 8 As shown in FIG. 1 , a plate-shaped test piece 40 including a region P, a thickness of 2 mm, a width of 10 mm, and a length of 75 mm was prepared. The thickness of the plate-shaped test piece 40 of 2 mm corresponds to the length in the weld metal thickness direction T, the length of the plate-shaped test piece 40 of 75 mm corresponds to the length in the weld metal width direction W, and the width of the plate-shaped test piece 40 of 10 mm corresponds to the length in the weld metal extension direction L. The plate-shaped test piece 40 was prepared so that the region P of the weld metal 20 was located at the center of the length of the plate-shaped test piece 40 of 75 mm.

[0571] The polythionic acid SCC resistance evaluation test was carried out in accordance with JIS G 0576:2001 "Stress corrosion cracking test method for stainless steel". Specifically, the plate-shaped test piece was bent around a punch with an inner radius of 5 mm to form a U-shaped bend (the bent portion corresponds to the weld metal). The U-shaped bent plate-shaped test piece was immersed in Wackenroder solution (by blowing SO into distilled water) at room temperature. 2 H 2 SO 3 A large amount of H 2 The plate-shaped test piece after immersion was immersed in a solution containing sulfur gas for 100 hours. The presence or absence of cracks in the weld metal portion of the plate-shaped test piece was observed under a microscope at a magnification of 500 times to confirm the presence or absence of cracks. The evaluation results are shown in Table 4. In the case where cracks were not confirmed in the weld metal portion of the test piece, it was judged that sufficient polythionic acid SCC resistance was obtained in the weld metal ("E" in Table 4). On the other hand, in the case where cracks were confirmed in the weld metal portion of the test piece, it was judged that sufficient polythionic acid SCC resistance was not obtained ("NA" in Table 4).

[0572] [(Test 4) Naphthenic Acid Corrosion Resistance Evaluation Test]

[0573] The naphthenic acid corrosion resistance of the weld metal of the austenitic stainless steel alloy weld joint of each weld metal number was evaluated by the following method. First, a weld metal test piece including the region P was collected from the austenitic stainless steel alloy weld joint of each weld metal number. Figure 8The plate-shaped test piece 40 shown in the figure is similarly manufactured to include a region P, a 3 mm thick, a 10 mm wide, and a 30 mm long test piece. The 3 mm thickness of the test piece corresponds to the length of the weld metal thickness direction T, the 30 mm length of the test piece corresponds to the length of the weld metal width direction W, and the 10 mm width of the test piece corresponds to the length of the weld metal extension direction L. The test piece is manufactured so that the region P is located in the center of the length direction of the test piece and in the center of the thickness direction.

[0574] The prepared test piece was placed under normal pressure and immersed in a 100% cyclohexane carbonate solution (test solution) at 200° C. for 720 hours. After the lapse of 720 hours, the test piece was taken out.

[0575] After 720 hours had passed, the test piece taken out was subjected to ultrasonic cleaning for 3 minutes using acetone.

[0576] The difference between the mass of the test piece before the test and the mass of the test piece after ultrasonic cleaning was calculated as the corrosion loss. In addition, the corrosion rate (mm / y) was calculated from the surface area, specific gravity, and test time of the test piece. The evaluation results are shown in Table 4. When the corrosion rate is 0.010 mm / y or less, it is judged that sufficient cyclopentane acid corrosion resistance is obtained in the weld metal. On the other hand, when the corrosion rate is greater than 0.010 mm / y, it is judged that sufficient cyclopentane acid corrosion resistance cannot be obtained.

[0577] [(Test 5) Aging toughness evaluation test]

[0578] The aging toughness of the weld metal of the austenitic stainless steel alloy welded joints of each weld metal number was evaluated in the following manner. Fig. 9 A V-notch test piece 50 including an area P was made for the austenitic stainless steel alloy weld joint of each weld metal number at the position shown. The width of the test piece 50 was set to 10 mm, the thickness was set to 10 mm, and the length was set to 55 mm. The thickness of the test piece 10 mm corresponds to the length of the weld metal thickness direction T, the width of the test piece 10 mm corresponds to the length of the weld metal width direction W, and the length of the test piece 55 mm corresponds to the length of the weld metal extension direction L. The test piece 50 was made in such a way that the area P of the weld metal 20 was located at the center of the width of the test piece 50. A V-shaped cut was formed at the center of the length of the test piece 50. The V-shaped cut angle was set to 45°, the cut depth was set to 2 mm, and the cut bottom radius was set to 0.25 mm. Three V-notch test pieces 50 were made.

[0579] The test piece 50 was subjected to an aging treatment at 650°C for 1000 hours. After being kept for 1000 hours, the test piece was naturally cooled to room temperature. The aging test piece was subjected to a Charpy impact test in accordance with JIS Z 2242:2005 at room temperature in the atmosphere. The three impact values ​​(J / cm 2 ) is defined as the impact value (J / cm 2 The evaluation results are shown in Table 4. If the impact value obtained is 20 J / cm 2 On the other hand, if the impact value obtained is less than 20 J / cm 2 , it is judged that sufficient aging toughness cannot be obtained in the weld metal.

[0580] [Test results]

[0581] Referring to Table 1-1, Table 1-2, Table 2-1, Table 2-2, Table 3-1, Table 3-2, and Table 4, in Test Nos. 1 to 25, the chemical compositions of the base material, welding material, and weld metal are appropriate, and the manufacturing conditions are also appropriate. Therefore, the austenitic stainless steel alloy welded joints of these Test Nos. satisfy Characteristics 1 to 4. Therefore, in these Test Nos., sufficient resistance to welding hot cracking, sufficient resistance to polythionic acid SCC, sufficient resistance to naphthenic acid corrosion, and sufficient aging toughness are obtained.

[0582] On the other hand, in test numbers 26 and 31, the Mo content of the welding material was too low. Therefore, the Mo content of the weld metal was too low. Therefore, sufficient naphthenic acid corrosion resistance could not be obtained.

[0583] In test numbers 27 and 28, the C content of the welding material was too high. Therefore, the C content of the weld metal was too high. Therefore, sufficient polythionic acid SCC resistance could not be obtained.

[0584] In test numbers 29 and 32, the Mo content of the welding material was too high. Therefore, the Mo content of the weld metal was too high. Therefore, in test number 29, sufficient aging toughness could not be obtained. Furthermore, in test number 32, F1 was greater than 2.30. Therefore, sufficient resistance to welding hot cracking could not be obtained.

[0585] In test numbers 30 and 33, the Ni content of the welding material was too low. Therefore, the Ni content of the weld metal was too low. Therefore, sufficient aging toughness could not be obtained.

[0586] In test number 34, the B content of the welding material was too high. Therefore, the B content of the weld metal was too high. Therefore, sufficient welding hot cracking resistance could not be obtained.

[0587] In test number 35, although the chemical compositions of the base material and the welding material were appropriate, the heat input of the welding conditions was too high. Therefore, F2 was greater than 2.5. As a result, sufficient naphthenic acid corrosion resistance and sufficient aging toughness could not be obtained.

[0588] In test number 36, the C content of the base material was too high. Therefore, the C content of the weld metal was too high. In addition, the interlayer temperature was higher than 150°C. Therefore, F2 was higher than 2.5. Therefore, sufficient polythionic acid SCC resistance, sufficient cyclopentane acid corrosion resistance, and sufficient aging toughness could not be obtained.

[0589] In test number 37, the B content of the base material was too high. Therefore, the B content of the weld metal was too high. Therefore, sufficient resistance to welding hot cracking could not be obtained.

[0590] In Test No. 38, the Mo content of the base material was too low. Therefore, the Mo content of the weld metal was too low. Therefore, sufficient naphthenic acid corrosion resistance could not be obtained.

[0591] In test numbers 39 and 40, although the chemical compositions of the base metal and the weld metal were appropriate, F1 exceeded 2.30, and therefore, sufficient resistance to welding hot cracking could not be obtained.

[0592] In test number 41, although the chemical compositions of the base material and the welding material were appropriate, the heat input and the interlayer temperature were both high. Therefore, F2 was greater than 2.5. As a result, sufficient naphthenic acid corrosion resistance and sufficient aging toughness could not be obtained.

[0593] In test number 42, although the chemical compositions of the base material and the welding material were appropriate, the heat input was too high. Therefore, F2 was greater than 2.5. As a result, sufficient naphthenic acid corrosion resistance and sufficient aging toughness could not be obtained.

[0594] In test number 43, although the chemical compositions of the base material and the welding material were appropriate, the interlayer temperature was too high. Therefore, F2 was greater than 2.5. As a result, sufficient naphthenic acid corrosion resistance and sufficient aging toughness could not be obtained.

[0595] In test No. 44, although the chemical compositions of the base material and the welding material were appropriate, FA was less than 0.60. Therefore, F2 was greater than 2.5. As a result, sufficient naphthenic acid corrosion resistance and sufficient aging toughness could not be obtained.

[0596] The embodiments of the present disclosure have been described above. However, the above embodiments are merely examples for implementing the present disclosure. Therefore, the present disclosure is not limited to the above embodiments, and the above embodiments can be appropriately modified and implemented within the scope of the present disclosure.

[0597] Description of Reference Numerals

[0598] 1. Austenitic stainless steel alloy welded joint; 10. Base material; 20. Weld metal.

Claims

1. An austenitic stainless steel alloy welded joint comprising a base material and a weld metal, wherein the chemical composition of the base material is, in mass %, C: 0.030% or less, Si: 0.10-1.00%, Mn: 0.20~2.00%, P: 0.040% or less, S: 0.010% or less, Cr:16.0~25.0%、 Ni: 10.0-30.0%, Mo: 0.1~5.0%, Nb: 0.20-1.00%, N:0.05~0.30%、 Sol.Al: 0.001~0.100%, B:0~0.0080%、 Cu: 0-5.00%, W:0~5.00%、 Co: 0-1.00%, V:0~1.00%、 Ta: 0~0.20% Hf: 0~0.20%, Ca: 0~0.010% Mg: 0~0.010%, Rare earth elements: 0 to 0.100%, and The balance is Fe and impurities. The chemical composition of the weld metal is, by mass%, C: 0.020% or less, Si: 0.01-1.00%, Mn: 0.20~2.00%, P: 0.030% or less, S: 0.010% or less, Cr:16.0~25.0%、 Ni: 15.0~40.0%, Mo: 2.5-5.0%, Nb: 0.10-2.00%, N:0.05~0.30%、 Sol.Al: 0.001~0.100%, B:0.0010~0.0050%、 Cu: 0-5.00%, W:0~5.00%、 Co: 0-1.00%, V:0~1.00%、 Ta: 0~0.20% Hf: 0~0.20%, Ca: 0~0.010% Mg: 0~0.010%, Rare earth elements: 0 to 0.100%, and The balance is Fe and impurities. The F1 of the weld metal defined by formula (1) is 2.30 or less, In a cross section of the weld metal perpendicular to the extending direction of the weld metal, a 1 mm × 1 mm square area at the width center of the surface of the weld metal and at the thickness center of the weld metal is divided into 100 μm × 100 μm micro-square areas, and the Mo content in mass % in each micro-square area is calculated. The arithmetic mean of all the Mo contents obtained is defined as [Mo] AVE , the ratio of the total Mo content obtained to the [Mo] AVE The arithmetic mean of the high Mo content is defined as [Mo] H , the ratio of the total Mo content obtained to the [Mo] AVE The arithmetic mean of the low Mo content is defined as [Mo] L hour, F2 defined by formula (2) is less than 2.5, F1=130B+8C+0.025Cr+0.25Mn+0.08Mo+0.6Nb+12P+7.6S+0.78Si+0.012W(1) F2=[You] H / [You] L (2) in, In the formula (1), the content of the corresponding element in the weld metal is substituted in mass %.

2. The austenitic stainless steel alloy weld joint according to claim 1, wherein: The chemical composition of the base material contains B:0.0001~0.0080%、 Cu: 0.01~5.00%, W:0.01~5.00%、 Co: 0.01~1.00%, V:0.01~1.00%、 Ta: 0.01~0.20% Hf: 0.01~0.20%, Ca: 0.001~0.010%, Mg: 0.001-0.010%, and Rare earth elements: one or more elements selected from the group consisting of 0.001 to 0.100%.

3. The austenitic stainless steel alloy weld joint according to claim 1 or 2, wherein: The chemical composition of the weld metal contains Cu: 0.01~5.00%, W:0.01~5.00%、 Co: 0.01~1.00%, V:0.01~1.00%、 Ta: 0.01~0.20% Hf: 0.01~0.20%, Ca: 0.001~0.010%, Mg: 0.001-0.010%, and Rare earth elements: one or more elements selected from the group consisting of 0 to 0.100%.

4. An austenitic stainless steel alloy welding material, the chemical composition of which is, by mass%, C: 0.020% or less, Si: 0.01-1.00%, Mn: 0.20~2.00%, P: 0.030% or less, S: 0.010% or less, Cr:16.0~25.0%、 Ni: 15.0~40.0%, Mo: 2.5-5.0%, Nb: 0.10-2.00%, N:0.05~0.30%、 Sol.Al: 0.001~0.100%, B:0.0010~0.0050%、 Cu: 0-5.00%, W:0~5.00%、 Co: 0-1.00%, V:0~1.00%、 Ta: 0~0.20%, Hf: 0~0.20%, Ca: 0~0.010% Mg: 0~0.010%, Rare earth elements: 0 to 0.100%, and The balance is Fe and impurities.

Citation Information

Cited By

  • Iron-based welding wire and method for austenitic stainless steel / carbon steel composite pipe CMT welding

    CN121848017A